Toner, toner storage unit, two-component developer, image forming apparatus, and image forming method
A toner composition with controlled resin ratios and glass transition temperatures addresses the challenge of balancing low-temperature fixing and heat-resistant preservation, enhancing image stability and durability in high-speed imaging processes.
Patent Information
- Application Number
- JP2023117980
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-30
AI Technical Summary
Existing toner technologies face challenges in balancing low-temperature fixing and heat-resistant preservation, particularly in high-speed imaging processes, leading to issues with image stability and durability under varying operating conditions.
A toner composition comprising specific ratios of polyester resins A, B, and C, along with a release agent and coloring agent, which includes insoluble and soluble components in tetrahydrofuran (THF), with controlled glass transition temperatures (TGA1ST, TGB1ST, and TG2ND) to ensure compatibility and stability.
The toner achieves stable image formation with balanced low-temperature fixing and heat-resistant preservation, ensuring high-quality images under continuous operation and environmental fluctuations.
Smart Images

Figure 2025014970000003 
Figure 2025014970000004 
Figure 2025014970000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner, a toner storage unit, a two-component developer, an image forming apparatus, and an image forming method. [Background technology]
[0002] In recent years, in image forming devices using a heat fixing method, a large amount of electricity is required in the process of thermally melting toner and fixing it on a recording medium such as paper. Therefore, from the perspective of saving energy, low-temperature fixability has become one of the important properties of a toner. However, since there is a tradeoff between low-temperature fixability and heat-resistant storage stability, it is an issue for a toner to achieve both low-temperature fixability and heat-resistant storage stability.
[0003] In order to achieve both low-temperature fixability and heat-resistant storage stability, a method for producing a toner by a polymerization method has been proposed. A toner produced by the polymerization method can be easily made small in particle size, has a sharper particle size distribution than a toner produced by a kneading and pulverizing method, and can also contain a release agent. As a method for producing a toner by a polymerization method, a method for producing a toner from an elongation reaction product of a urethane-modified polyester as a toner binder has been proposed for the purpose of improving low-temperature fixing properties and high-temperature offset resistance (see, for example, Patent Document 1).
[0004] However, in recent years, the demand for low-temperature fixability has become higher, and in order to meet this demand, a toner has been proposed that contains a resin including a crystalline polyester resin and a release agent, and has a sea-island phase-separated structure in which the resin and the wax are incompatible with each other (see, for example, Patent Document 2). Also, a toner has been proposed that contains a crystalline polyester resin, a release agent, and a graft polymer (see, for example, Patent Document 3). Also, a toner that contains predetermined amorphous polyester resins A and B and a crystalline polyester resin C and has excellent low-temperature fixability, heat-resistant storage stability, and high-temperature / high-humidity storage stability has been proposed (see, for example, Patent Documents 4 to 7).
[0005] Since crystalline polyester resin melts more rapidly than amorphous polyester resin, it is possible to ensure heat-resistant storage stability while exhibiting low-temperature fixability by finely dispersing it in toner particles. However, the demand for low-temperature fixability of toners is increasing along with energy saving, and from the viewpoint of cost and productivity, the trend to use common supplies from low-speed machines to ultra-high-speed machines such as production machines is accelerating, and a high level of heat-resistant storage stability is also being demanded so that the toner can withstand more severe use.
[0006] In addition, there is an extremely high demand for high image quality and high stability in production machines, and toner is also required to have a high level of charge stability so that high-quality images can be stably output under any operating conditions or usage environment. However, no technology has yet been proposed that can fully solve these issues. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a toner which has both low-temperature fixability and heat-resistant storage stability, and is also excellent in charge stability. [Means for solving the problem]
[0008] The present invention, which solves the above problems, relates to a toner for developing electrostatic images as described below. A toner for developing an electrostatic image, comprising a toner base and an external additive attached to a surface of the toner base, The toner base contains at least a binder resin, a colorant, and a release agent. The toner contains a component insoluble in tetrahydrofuran (THF) and a component soluble in THF, The components of the toner that are insoluble in tetrahydrofuran (THF) are observed at two points, Tga1st and Tgb1st, in the first temperature rise of differential scanning calorimetry (DSC), The Tga1st is -40°C or more and 10°C or less, and the Tgb1st is 45°C or more and 65°C or less, A toner for developing electrostatic images, characterized in that the amount of residual surfactant in the toner as detected by liquid chromatography / mass spectrometry (LC / MS) is 800 ppm or more and 1,200 ppm or less. Effect of the Invention
[0009] The toner of the present invention achieves both low-temperature fixability for achieving energy saving and heat-resistant storage stability, which is in a trade-off relationship with this, and further has excellent charging stability during continuous operation and against environmental fluctuations, making it possible to form stable, high-quality images. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a diagram for explaining how to determine Tg in a DSC curve. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge. [Diagram 3] FIG. 3 is a schematic diagram showing an example of an image forming apparatus according to the present invention. [Figure 4] FIG. 4 is a partially enlarged view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] (toner) The toner of the present invention will now be described. Furthermore, it is easy for a person skilled in the art to modify and alter the present invention within the scope of the claims to create other embodiments, and these modifications and alterations are intended to be included in the scope of the claims. The following description is an example of the best mode of the present invention and is not intended to limit the scope of the claims.
[0012] The characteristics of the toner used in the image forming method according to this embodiment will be described below. The toner of the present invention is an electrostatic image developing toner comprising a toner base and an external additive attached to the surface of the toner base. The toner base contains at least a binder resin, a colorant, and a release agent. The toner contains a component insoluble in tetrahydrofuran (THF) and a component soluble in THF, and is characterized in that the amount of residual surfactant in the toner detected by liquid chromatography / mass spectrometry (LC / MS) is 800 ppm or more and 1,200 ppm or less.
[0013] When the amount of the residual surfactant in the toner is within the above range, the toner surface becomes soft, which is advantageous in that it aids in low-temperature fixability. If the amount of the residual surfactant in the toner is less than 800 ppm, this auxiliary function is not realized. Also, if the amount of the residual surfactant in the toner exceeds 1,200 ppm, there are disadvantages in that the charging stability deteriorates and the storage stability cannot be guaranteed due to the softening of the toner particles.
[0014] The toner used in the present invention is characterized in that the components insoluble in tetrahydrofuran (THF) are observed at two glass transition temperatures (Tg1st) in the first heating step of differential scanning calorimetry (DSC), Tga1st being in the range of -40°C or more and 10°C or less, and Tgb1st being in the range of 45°C or more and 65°C or less.
[0015] The THF-insoluble component is preferably a polyester resin. In the present invention, the components resulting from the two glass transition temperatures Tga1st and Tgb1st in the first heating run of the DSC are referred to as polyester resin A and polyester resin B, respectively. In the present invention, the component soluble in THF of the toner is determined as polyester resin C, which is caused by the glass transition temperature (Tg2nd) at the second temperature rise in DSC.
[0016] Polyester resin A and polyester resin B are components derived from a large amorphous polyester resin having a weight average molecular weight (Mw) of 100,000 to 200,000, and the THF-soluble polyester resin C is a component derived from an amorphous polyester resin having a weight average molecular weight (Mw) of 3,000 to 10,000.
[0017] In the present invention, the glass transition temperature is defined as follows. Tg1st: glass transition temperature of the toner at the first temperature rise Tg2nd: glass transition temperature of the toner at the second heating Tga1st: glass transition temperature of the THF insoluble component in the toner at the first temperature rise Tgb1st: Glass transition temperature of the THF insoluble component in the toner at the first temperature rise
[0018] In addition, unless otherwise specified, the melting points and glass transition temperatures Tg of the polyester resins A, B, and C, the release agent, and other constituent components are the endothermic peak top temperature and glass transition temperature Tg2nd during the second heating, respectively, of each sample.
[0019] Polyester resin A imparts plasticity to the toner. The polyester resin A in the toner of the present invention, which is insoluble in tetrahydrofuran (THF), lowers the Tg and melt viscosity and ensures low-temperature fixability, and has a branched structure in the molecular skeleton and a three-dimensional network structure in the molecular chain, so that the toner has rubber-like properties in that it deforms at low temperatures but does not flow.
[0020] Conventional techniques (see, for example, Patent Document 4) have attempted to solve the problem by optimizing the ratio of polyester resin A to polyester resin C. However, if too much polyester resin A is added, Tg decreases and storage stability cannot be guaranteed. In addition, the stress resistance of the toner deteriorates, and the fluidizing agent on the toner surface is buried due to the thermal and mechanical stress caused by stirring in the developing device, and the adhesion of the toner particles increases. As a result, there is a concern that defects such as image blurring may occur in the transfer process. On the other hand, if the amount of polyester resin A is too small, the plasticity is not imparted sufficiently and low-temperature fixability cannot be satisfied. In addition, there is a concern that the necessary elasticity is not imparted, high-temperature offset is deteriorated, the fixable area is narrowed, and the image glossiness is too high.
[0021] In the present invention, by using polyester resin B, which has a Tg similar to that of the toner and does not deviate significantly from that of the toner, and which provides elasticity, it is possible to increase the elasticity of the toner without affecting heat resistance, ensure the offset range, and control the image gloss in an appropriate range while preventing image graininess. However, although the cause is unclear, it was found that when mixed at an arbitrary ratio, the resins separate, causing poor pigment dispersion and reducing the coloring degree. It was found that by determining polyester resins A, B, and C so that the component ratio is appropriate, it is possible to ensure the fixing range and storage stability without reducing the coloring degree, and a better toner can be obtained.
[0022] In addition, when preparing the oil phase, the raw materials constituting the oil phase can be finely and uniformly arranged in the oil droplets by adding a homogenization process in addition to the conventional dissolving process, and in particular, modified layered inorganic minerals can be efficiently arranged on the toner surface even with a small formulation amount. This makes it possible to achieve both low-temperature fixability and heat-resistant storage stability without impairing the properties of the polyester resins A, B, and C, and to suppress deterioration of charging stability due to an increase in the amount of residual surfactant in the toner. However, if the amount of the residual surfactant in the toner is more than 1,200 ppm, the deterioration of the charging stability cannot be suppressed. Although the reason is not clear, the amount of the residual surfactant in the toner is inversely proportional to the formulation amount of the surfactant. By adding the homogenization step, the same granulation properties can be obtained as in the case where the homogenization step is not performed even if the formulation amount of the surfactant is reduced, but the amount of the surfactant remaining in the toner increases. On the other hand, when the homogenization step is not carried out, it is necessary to increase the amount of surfactant used in the formulation, as compared with the case where the homogenization step is carried out. Therefore, by adjusting the formulation amount of the surfactant while taking into consideration the granulation property, it is possible to keep the amount of the surfactant remaining in the toner within a target range to some extent.
[0023] Here, a method for measuring the amount of the residual surfactant in the toner will be described in detail. The amount of the residual surfactant in the toner is measured by liquid chromatography / mass spectrometry (LC / MS method). The AQUITY UPLC / SQD2 System (manufactured by Waters) can be used as the analytical device. This analytical device uses the "AQUITY SQD2" as the mass spectrometry (MS) device and the "ACQUITY UPLC" as the liquid chromatography (LC) device. In addition, the "ACQUITY UPLC BEH C18 Column, 130 Å (manufactured by Waters)" can be used as the column for liquid chromatography. 1. Sample Preparation Samples for creating a calibration curve are prepared with surfactant amounts of 10 ppm, 5 ppm, 2 ppm, and 1 ppm. A toner sample is prepared by diluting 0.1 g of toner with 10 mL of MeOH. The calibration curve sample and toner sample were placed in an ultrasonic cleaner (W-113MKII) for 30 minutes (explosive cleaning mode). Filter through a 0.45 μm filter and transfer to a sample vial. Place the sample vial in the sample holder.
[0024] 2. Measurement 1.0 μL of the sample was injected for measurement, and the area of the main peak (surfactant) of the sample was determined. The content of the surfactant in the toner was calculated by plotting it on a calibration curve of the peak area and concentration of the surfactant prepared in advance using calibration curve samples. <LC Conditions> Analysis column: ACQUITY UPLC BEH C18 Column, 130 Å, 1.7 μm, 2.1 mm × 50 mm Column temperature: 40 °C Mobile phase A: 75% distilled water Mobile phase B: 25% methanol Flow rate: 0.25 mL / min Detector: AQUITY SQD2 Ionization method: ESI Measured ion: negative ion Capillary voltage: 3.5 kV Sheath Gas flow: 50
[0025] <Polyester resin A> Polyester resin A is a resin insoluble in tetrahydrofuran (THF). Polyester resin A preferably contains a polyhydric alcohol component and a polycarboxylic acid component as constituent components, and the polyhydric alcohol component is preferably a diol component.
[0026] Examples of the diol component include aliphatic diols having 3 to 10 carbon atoms. Examples of the aliphatic diol having 3 to 10 carbon atoms include 1,2 - propylene glycol, 1,3 - propylene glycol, 1,4 - butanediol, 2 - methyl - 1,3 - propanediol, 1,5 - pentanediol, 3 - methyl - 1,5 - pentanediol, 1,6 - hexanediol, 1,8 - octanediol, 1,10 - decanediol, 1,12 - dodecanediol, etc. The aliphatic diol having 3 to 10 carbon atoms preferably contains 50 mol% or more, and more preferably 80 mol% or more.
[0027] The diol component of the polyester resin A preferably has an odd carbon number of 3 to 9 in the main chain and an alkyl group in the side chain, and more preferably has a structure represented by the following general formula (1). HO-(CR 1 R 2 )n-OH General formula (1) In the above formula, R 1 and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an odd number from 3 to 9. In the n repeating units, R 1 and R 2 may be the same or different.
[0028] In addition, the polyester resin A preferably contains a crosslinking component. As the crosslinking component, it is preferable to contain a trihydric or higher aliphatic alcohol component, and from the viewpoint of the gloss and image density of the fixed image, it is more preferable to contain a trihydric or tetrahydric aliphatic alcohol component. As the trihydric or tetrahydric aliphatic alcohol component, it is preferable to use a trihydric or tetrahydric aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. The crosslinking component may be only the trihydric or higher aliphatic alcohol.
[0029] The trihydric or higher aliphatic alcohol can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, dipentaerythritol, etc. These trihydric or higher aliphatic alcohols may be used alone or in combination of two or more kinds.
[0030] As the crosslinking component of polyester resin A, a trivalent or higher carboxylic acid or an epoxy compound, etc. can be used. However, from the viewpoint of preventing unevenness and obtaining sufficient gloss and image density, it is more preferable to contain a trivalent or higher aliphatic alcohol as the crosslinking component.
[0031] The proportion of the crosslinking component in the constituent components of the polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass to 5% by mass, more preferably 1% by mass to 3% by mass. The proportion of the trihydric or higher aliphatic alcohol in the polyhydric alcohol component that is a constituent of the polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50% by mass to 100% by mass, and more preferably 90% by mass to 100% by mass.
[0032] The dicarboxylic acid component of the polyester resin A preferably contains an aliphatic dicarboxylic acid having 4 to 12 carbon atoms in an amount of 50 mol % or more. Examples of the aliphatic dicarboxylic acid having 4 to 12 carbon atoms include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid. In addition, it is preferable that polyester resin A has a urethane bond and / or a urea bond in order to provide better adhesion to recording media such as paper, whereby the urethane bond or urea bond behaves like a pseudo-crosslinking point, the rubber-like properties of polyester resin A are strengthened, and the toner has better heat-resistant storage stability and high-temperature offset resistance.
[0033] The molecular weight of polyester resin A is not particularly limited and can be appropriately selected according to the purpose. However, if the molecular weight is too low, the toner may have poor heat-resistant storage stability and poor durability against stress such as stirring in a developing machine, while if the molecular weight is too high, the toner may have high viscoelasticity when melted and poor low-temperature fixability. Therefore, it is preferable that the weight-average molecular weight (Mw) is 100,000 to 200,000 as measured by GPC (gel permeation chromatography).
[0034] The Tg of the polyester resin A is -50°C or more and 0°C or less, and preferably -40°C or more and -20°C or less. If the Tg is less than -50°C, the toner has poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has poor filming resistance. On the other hand, if the Tg is more than 0°C, the toner is not deformed sufficiently by heating and pressure during fixing, and the low-temperature fixing property is insufficient.
[0035] <Polyester resin B> Polyester resin B is a resin insoluble in tetrahydrofuran (THF). The polyester resin B preferably contains a polyhydric alcohol component and a polycarboxylic acid component. The polyester resin B is preferably a modified polyester containing an ester bond and a bond unit other than the ester bond, and the binder resin precursor is preferably a resin precursor capable of producing the modified polyester.
[0036] Examples of the polyhydric alcohol component include alkylene glycols (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, etc.); alkylene ether glycols (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); alicyclic diols (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.); bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.); alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above alicyclic diols; and alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above bisphenols, and two or more of these may be used in combination. Among these, alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols (for example, bisphenol A ethylene oxide 2-mol adduct, bisphenol A propylene oxide 2-mol adduct, bisphenol A propylene oxide 3-mol adduct, etc.) are preferred.
[0037] Examples of trihydric or higher polyols include polyhydric aliphatic alcohols (glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc.); trihydric or higher phenols (phenol novolac, cresol novolac, etc.); alkylene oxide adducts of trihydric or higher polyphenols; and the like, and two or more of these may be used in combination.
[0038] Examples of the divalent carboxylic acid component include alkylene dicarboxylic acids (succinic acid, adipic acid, sebacic acid, etc.), alkenylene dicarboxylic acids (maleic acid, fumaric acid, etc.), aromatic dicarboxylic acids (terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, etc.), and the like, and two or more of them may be used in combination. Among them, alkenylene dicarboxylic acids having 4 to 20 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms are preferred. Examples of trivalent or higher polycarboxylic acids include aromatic polycarboxylic acids having 9 to 20 carbon atoms (eg, trimellitic acid, pyromellitic acid, etc.), and two or more of these may be used in combination. Instead of the polycarboxylic acid, anhydrides or lower alkyl esters (methyl esters, ethyl esters, isopropyl esters, etc.) of polycarboxylic acids may be used.
[0039] In addition, it is preferable that polyester resin B has a urethane bond and / or a urea bond in order to provide better adhesion to recording media such as paper, etc. This allows the urethane bond or urea bond to behave like a pseudo-crosslinking point, strengthens the rubber-like properties of polyester resin B, and provides better heat-resistant storage stability and high-temperature offset resistance of the toner.
[0040] The Tg of polyester resin B is 45° C. or more and 65° C. or less, and preferably 50° C. or more and 60° C. or less. If the Tg is less than 45° C., the toner has poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has poor filming resistance. On the other hand, if the Tg is more than 65° C., the toner is not deformed sufficiently by heating and pressure during fixing, and the low-temperature fixing property is insufficient.
[0041] <Polyester resin C> Polyester resin C is a resin soluble in tetrahydrofuran (THF). The polyester resin C preferably contains a diol component and a dicarboxylic acid component as constituent components, and preferably contains 40 mol % or more of alkylene glycol. The polyester resin C may or may not contain a crosslinking component as a constituent component. The polyester resin C is preferably a linear polyester resin.
[0042] Moreover, an unmodified polyester resin is preferable as the polyester resin C. The unmodified polyester resin is a polyester resin obtained using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic acid anhydride, or a polycarboxylic acid ester, and is not modified with an isocyanate compound or the like.
[0043] Examples of the polyhydric alcohol include diols. Examples of the diol include alkylene (carbon number 2 to 3) oxide (average number of moles added: 1 to 10) adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane and polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, propylene glycol; hydrogenated bisphenol A, and alkylene (carbon number 2 to 3) oxide (average number of moles added: 1 to 10) adducts of hydrogenated bisphenol A. These may be used alone or in combination of two or more.
[0044] Examples of the polycarboxylic acid include dicarboxylic acids. Examples of the dicarboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, and succinic acids substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms, such as dodecenylsuccinic acid and octylsuccinic acid. In particular, it is preferable that the monomer contains 50 mol % or more of terephthalic acid. These may be used alone or in combination of two or more.
[0045] Furthermore, the polyester resin C may contain a trivalent or higher carboxylic acid and / or a trivalent or higher alcohol at the end of its resin chain in order to adjust the acid value and hydroxyl value. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and acid anhydrides thereof. Examples of the trihydric or higher alcohol include glycerin, pentaerythritol, and trimethylolpropane.
[0046] The polyester resin C preferably contains a crosslinking component. The crosslinking component preferably contains a trivalent or higher aliphatic alcohol, and from the viewpoint of the gloss and image density of the fixed image, more preferably contains a trivalent or tetravalent aliphatic alcohol. The trivalent or tetravalent aliphatic alcohol is preferably a trivalent or tetravalent aliphatic polyalcohol component having 3 to 10 carbon atoms. The crosslinking component may be only the trivalent or higher aliphatic alcohol.
[0047] The trihydric or higher aliphatic alcohol can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, dipentaerythritol, etc. These trihydric or higher aliphatic alcohols may be used alone or in combination of two or more kinds.
[0048] As the crosslinking component of polyester resin C, a trivalent or higher carboxylic acid or an epoxy compound, etc. can be used. However, from the viewpoint of preventing unevenness and obtaining sufficient gloss and image density, it is more preferable to contain a trivalent or higher aliphatic alcohol as the crosslinking component.
[0049] The molecular weight of polyester resin C is not particularly limited and can be appropriately selected according to the purpose. However, if the molecular weight is too low, the toner may have poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and if the molecular weight is too high, the viscoelasticity of the toner when melted may increase and the low-temperature fixability may be poor. In addition, if the amount of the component having a molecular weight of 600 or less is too large, the toner may have poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and if the amount of the component having a molecular weight of 600 or less is too small, the low-temperature fixability may be poor. Therefore, in the GPC (gel permeation chromatography) measurement, the weight average molecular weight (Mw) is preferably 3,000 to 10,000, and the number average molecular weight (Mn) is preferably 1,000 to 4,000. Also, Mw / Mn is preferably 1.0 to 4.0. Also, the weight average molecular weight (Mw) is more preferably 4,000 to 7,000, the number average molecular weight (Mn) is more preferably 1,500 to 3,000, and the Mw / Mn is more preferably 1.0 to 3.5. Furthermore, the THF-soluble component having a molecular weight of 600 or less is preferably 2 to 10% by mass, and the polyester resin C may be purified by extracting it with methanol to remove the component having a molecular weight of 600 or less.
[0050] The acid value of the polyester resin C is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1 mgKOH / g to 50 mgKOH / g, more preferably 5 mgKOH / g to 30 mgKOH / g. When the acid value is 1 mgKOH / g or more, the toner tends to be negatively charged, and furthermore, the affinity between the paper and the toner is improved when fixing to the paper, and low-temperature fixing property can be improved. On the other hand, when the acid value is more than 50 mgKOH / g, the charging stability, especially the charging stability against environmental changes, may decrease. The hydroxyl value of the polyester resin C is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 5 mgKOH / g or more.
[0051] The Tg of the polyester resin C is 45° C. to 65° C., preferably 50° C. to 60° C. If the Tg is less than 45° C., the toner has poor heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has poor filming resistance. On the other hand, if the Tg is more than 65° C., the toner is not deformed sufficiently by heating and pressure during fixing, and the low-temperature fixing property is insufficient.
[0052] The content of polyester resin C is preferably 80 parts by mass or more and 90 parts by mass or less, and more preferably 80 parts by mass, relative to 100 parts by mass of toner. In the case of a three-component system such as polyester resin A, polyester resin B, and polyester resin C as in the present invention, although the cause is not clear, if the content of polyester resin C is less than 80 parts by mass, polyester resin A and polyester resin B may separate, causing deterioration in dispersibility of the pigment in the toner and decreasing the coloring degree of the toner.
[0053] <Polyester resin having urethane bond and / or urea bond> The polyester resin having the urethane bond and / or urea bond is not particularly limited and can be appropriately selected according to the purpose. An example thereof is a reaction product of a polyester resin having an active hydrogen group and a polyisocyanate. This reaction product is preferably used as a reaction precursor (hereinafter sometimes referred to as a "prepolymer") to be reacted with a curing agent described later. Examples of the polyester resin having an active hydrogen group include polyester resins having a hydroxyl group.
[0054] -Polyisocyanate- The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyisocyanate include diisocyanates and tri- or higher valent isocyanates. Examples of the diisocyanate include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, isocyanurates, and those blocked with phenol derivatives, oximes, caprolactams, and the like.
[0055] Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, methyl 2,6-diisocyanatocaproate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, tetradecamethylene diisocyanate, trimethylhexane diisocyanate, and tetramethylhexane diisocyanate.
[0056] Examples of the alicyclic diisocyanate include isophorone diisocyanate and cyclohexylmethane diisocyanate.
[0057] Examples of the aromatic diisocyanate include tolylene diisocyanate, diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4'-diisocyanatodiphenyl, 4,4'-diisocyanato-3,3'-dimethyldiphenyl, 4,4'-diisocyanato-3-methyldiphenylmethane, and 4,4'-diisocyanato-diphenyl ether. Examples of the aromatic aliphatic diisocyanate include α,α,α',α'-tetramethylxylylene diisocyanate.
[0058] Examples of the isocyanurates include tris(isocyanatoalkyl)isocyanurate, tris(isocyanatocycloalkyl)isocyanurate, and the like. These polyisocyanates may be used alone or in combination of two or more kinds.
[0059] - Hardener - The curing agent is not particularly limited as long as it reacts with the prepolymer, and may be appropriately selected depending on the purpose. For example, an active hydrogen group-containing compound may be used.
[0060] --Compounds containing active hydrogen groups-- The active hydrogen group in the active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include hydroxyl groups (alcoholic hydroxyl groups and phenolic hydroxyl groups), amino groups, carboxyl groups, mercapto groups, etc. These may be used alone or in combination of two or more.
[0061] As the active hydrogen group-containing compound, amines are preferred because they are capable of forming a urea bond. Examples of the amines include diamines, trivalent or higher amines, amino alcohols, amino mercaptans, amino acids, blocked amino groups of these, etc. These may be used alone or in combination of two or more. Among these, diamines or mixtures of diamines with small amounts of trivalent or higher amines are preferred.
[0062] Examples of the diamine include aromatic diamines, alicyclic diamines, and aliphatic diamines. Examples of the aromatic diamines include phenylenediamine, diethyltoluenediamine, and 4,4'-diaminodiphenylmethane. Examples of the alicyclic diamines include 4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminocyclohexane, and isophoronediamine. Examples of the aliphatic diamines include ethylenediamine, tetramethylenediamine, and hexamethylenediamine.
[0063] Examples of the trivalent or higher amine include diethylenetriamine and triethylenetetramine. Examples of the amino alcohol include ethanolamine and hydroxyethylaniline. Examples of the amino mercaptan include aminoethyl mercaptan and aminopropyl mercaptan.
[0064] Examples of the amino acid include aminopropionic acid and aminocaproic acid. Examples of the blocked amino group include ketimine compounds and oxazoline compounds obtained by blocking the amino group with ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.
[0065] The molecular structures of the polyester resins A, B, C, etc. can be confirmed by NMR measurement in solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 and 990±10cm -1 One method is to detect polyester resins that do not have absorption due to olefin δCH (out-of-plane bending vibration).
[0066] <Crystalline polyester resin D> The toner of the present invention more preferably contains a crystalline resin as the resin. The crystalline resin will be described by taking crystalline polyester resin D (hereinafter, referred to as crystalline polyester resin). The crystalline polyester resin has high crystallinity and exhibits a thermal melting characteristic that shows a rapid viscosity drop near the fixing start temperature. By using a crystalline polyester resin having such characteristics together with the polyester resin, the heat-resistant storage stability due to crystallinity is good until just before the melting start temperature, and a rapid viscosity drop (sharp melt) due to melting of the crystalline polyester resin can be caused at the melting start temperature. Then, the crystalline polyester resin is compatible with the polyester resin, and both are fixed by a rapid viscosity drop, so that a toner having both good heat-resistant storage stability and low-temperature fixing ability can be obtained. In addition, the mold release width (the difference between the minimum fixing temperature and the high-temperature offset occurrence temperature) also shows good results.
[0067] The crystalline polyester resin can be obtained by using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester. In the present invention, the crystalline polyester resin refers to a resin obtained by using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, as described above. Modified polyester resins, such as the prepolymers and resins obtained by subjecting the prepolymers to a crosslinking and / or elongation reaction, do not belong to the crystalline polyester resins.
[0068] The presence or absence of crystallinity of the crystalline polyester resin in the present invention can be confirmed by a crystal analysis X-ray diffraction device (for example, X'Pert Pro MRD Philips). The measurement method is described below. First, the target sample is ground in a mortar to prepare a sample powder, and the obtained sample powder is evenly applied to a sample holder. After that, the sample holder is set in the diffraction device, and measurements are performed to obtain a diffraction spectrum. If the peak half-width of the peak with the highest peak intensity among the peaks obtained in the range of 20°<2θ<25° is 2.0 or less, it is determined to have crystallinity. In contrast to crystalline polyester resins, polyester resins that do not exhibit the above-mentioned state are referred to as amorphous polyester resins in the present invention. An example of the conditions for measuring X-ray diffraction is given below.
[0069] [Measurement conditions] Tension kV: 45kV Current: 40mA MPSS Upper Gonio Scan mode: continuos Start angle: 3° End angle: 35° Angle Step: 0.02° Lucident beam optics Divergence slit: Div slit 1 / 2 Diffraction beam optics Anti scatter slit: As fixed 1 / 2 Receiving slit: Prog rec slit
[0070] -Polyhydric alcohol- The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyhydric alcohol include diols and trihydric or higher alcohols.
[0071] Examples of the diol include saturated aliphatic diols. Examples of the saturated aliphatic diol include linear saturated aliphatic diols and branched saturated aliphatic diols. Among these, linear saturated aliphatic diols are preferred, and linear saturated aliphatic diols having 2 to 12 carbon atoms are more preferred. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in melting point. In addition, if the carbon number of the saturated aliphatic diol exceeds 12, it becomes difficult to obtain a practical material. It is more preferred that the carbon number is 12 or less.
[0072] Examples of the saturated aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-eicosanedecanediol, etc. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred in terms of the high crystallinity and excellent sharp melting properties of the crystalline polyester resin. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.
[0073] -Polycarboxylic acids- The polyvalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyvalent carboxylic acid include divalent carboxylic acids and trivalent or higher carboxylic acids.
[0074] Examples of the divalent carboxylic acid include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; and aromatic dicarboxylic acids such as dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid; and further, anhydrides of these acids and lower (carbon number: 1 to 3) alkyl esters of these acids.
[0075] Examples of the trivalent or higher carboxylic acid include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as anhydrides and lower (carbon number 1 to 3) alkyl esters thereof.
[0076] The polycarboxylic acid may contain a dicarboxylic acid having a sulfonic acid group in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. Furthermore, the polycarboxylic acid may contain a dicarboxylic acid having a double bond in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. These may be used alone or in combination of two or more.
[0077] The crystalline polyester resin is preferably composed of a linear saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a linear saturated aliphatic diol having 2 to 12 carbon atoms. That is, the crystalline polyester resin preferably has a structural unit derived from a saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a structural unit derived from a saturated aliphatic diol having 2 to 12 carbon atoms. This is preferable in that the resin has high crystallinity and excellent sharp melting properties, and can therefore exhibit excellent low-temperature fixability.
[0078] The melting point of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 60° C. to 80° C. If the melting point is less than 60° C., the crystalline polyester resin is likely to melt at low temperatures, and the heat-resistant storage stability of the toner may decrease, whereas if the melting point is more than 80° C., the crystalline polyester resin is not sufficiently melted by heating during fixing, and the low-temperature fixability may decrease.
[0079] The molecular weight of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose. From the viewpoint that a low molecular weight resin with a sharp molecular weight distribution has excellent low-temperature fixability, and a large amount of low molecular weight components reduces heat-resistant storage stability, the crystalline polyester resin preferably has a weight average molecular weight (Mw) of 3,000 to 30,000, a number average molecular weight (Mn) of 1,000 to 10,000, and Mw / Mn of 1.0 to 10, as measured by GPC. More preferably, the weight average molecular weight (Mw) is 5,000 to 15,000, the number average molecular weight (Mn) is 2,000 to 10,000, and Mw / Mn is 1.0 to 5.0.
[0080] The acid value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint of affinity between paper and resin, in order to achieve the desired low-temperature fixability, it is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, while in order to improve high-temperature offset resistance, it is preferably 45 mgKOH / g or less.
[0081] The hydroxyl value of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose. In order to achieve the desired low-temperature fixability and good charging characteristics, the hydroxyl value is preferably 0 mgKOH / g or more and 50 mgKOH / g or less, and more preferably 5 mgKOH / g or more and 50 mgKOH / g or less.
[0082] The molecular structure of the crystalline polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 Or 990±10cm -1 One method is to detect a crystalline polyester resin that has absorption based on the δCH (out-of-plane bending vibration) of olefin.
[0083] The content of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 2 parts by mass or more and 4 parts by mass or less, relative to 100 parts by mass of the toner. If the content is less than 1 part by mass, the sharp melting by the crystalline polyester resin is insufficient, so that the low-temperature fixing property may be poor, and if it exceeds 10 parts by mass, the heat-resistant storage stability may be reduced and the image may be easily fogged. If the content is within the above more preferred range, it is advantageous in that both high image quality and low-temperature fixing property are excellent.
[0084] <Other ingredients> In addition to the above-mentioned components, the toner of the present invention may contain other components such as a release agent, a colorant, a charge control agent, an external additive, a flowability improver, a cleaning property improver, and a magnetic material, if necessary.
[0085] -Release agent- The release agent is not particularly limited and can be appropriately selected from known agents. Examples of wax and wax release agents include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, and wood wax rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusin; and petroleum waxes such as paraffin, microcrystalline, and petrolatum.
[0086] In addition to these natural waxes, examples of the wax include Fischer-Tropsch wax, synthetic hydrocarbon waxes such as polyethylene and polypropylene, and synthetic waxes such as esters, ketones and ethers. Further, fatty acid amide compounds such as 12-hydroxystearic acid amide, stearic acid amide, phthalimide anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, a copolymer of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups in their side chains may be used.
[0087] Among these, hydrocarbon waxes such as paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, and polypropylene wax are preferred. The melting point of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 60° C. or more and 80° C. or less. If the melting point is less than 60° C., the release agent may melt easily at low temperatures and may have poor heat resistance storage stability. On the other hand, if the melting point is more than 80° C., even if the resin melts and is in the fixing temperature range, the release agent may not melt sufficiently, causing fixing offset and image defects.
[0088] The content of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 2 parts by mass to 10 parts by mass, more preferably 3 parts by mass to 8 parts by mass, relative to 100 parts by mass of toner. If the content is less than 2 parts by mass, the high-temperature offset resistance and low-temperature fixability during fixing may be poor, and if it exceeds 10 parts by mass, the heat-resistant storage stability may be reduced and image fogging may be easily caused. If the content is within the above more preferred range, it is advantageous in terms of improving image quality and fixing stability.
[0089] -Coloring agent- The colorant is not particularly limited and can be appropriately selected depending on the purpose. Examples include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, isoindolinone yellow, red iron oxide, red lead, vermilion, cadmium red Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Carmine BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belcan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluigi Bon Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalosyl Anthracite Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake, Malachite Green Lake, Phthalocyanine Green, Anthraquinone Green,Examples include titanium oxide, zinc oxide, and lithopone.
[0090] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 part by mass to 15 parts by mass, more preferably 3 parts by mass to 10 parts by mass, based on 100 parts by mass of the toner.
[0091] The colorant can also be used as a masterbatch composited with a resin. Examples of the resin used to manufacture the masterbatch or the resin kneaded with the masterbatch include, in addition to the polyester resin, styrene or a polymer of a substitute thereof, such as polystyrene, poly-p-chlorostyrene, or polyvinyltoluene; styrene-p-chlorostyrene copolymer, styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-α-chloromethyl ... styrene-based copolymers such as styrene-acrylonitrile copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-acrylonitrile-indene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resins, epoxy polyol resins, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin wax.
[0092] These may be used alone or in combination of two or more. The master batch can be obtained by mixing and kneading the resin for the master batch and the colorant under high shear force. In this case, an organic solvent can be used to enhance the interaction between the colorant and the resin. In addition, a method called a flushing method, in which an aqueous paste containing water of the colorant is mixed and kneaded with the resin and the organic solvent to transfer the colorant to the resin side and remove the water and organic solvent components, is also preferable because it does not require drying since the wet cake of the colorant can be used as it is. A high shear dispersion device such as a three-roll mill is preferably used for mixing and kneading.
[0093] -Charge control agent (modified layered inorganic minerals)- The modified layered inorganic mineral used in the toner of the present invention is not particularly limited, but is preferably one having a basic smectite crystal structure modified with an organic cation. In addition, when the layered inorganic mineral is a hydrotalcite, a part of the divalent metal is replaced with a trivalent metal, so that the ion balance is balanced to allow the introduction of anions. By introducing an organic anion into the layered inorganic mineral in this state, a layered inorganic compound modified with an organic anion can also be used.
[0094] By modifying at least a portion of the layered inorganic mineral with an organic ion, the mineral has a suitable hydrophobicity, and the oil phase containing the toner composition and / or the toner composition precursor has a non-Newtonian viscosity, making it possible to deform the toner.
[0095] Examples of layered inorganic minerals modified with organic cations include montmorillonite or bentonite, beidellite, nontronite, saponite, hectorite, attapulgite, sepiolite, and mixtures thereof. Among these, organically modified montmorillonite or bentonite is preferred because it does not affect the toner properties, allows easy viscosity adjustment, and allows the amount added to be small.
[0096] The organic cation modifier of the modified layered inorganic mineral may be a quaternary alkyl ammonium salt, a phosphonium salt, an imidazolium salt, etc., and preferably a quaternary alkyl ammonium salt. Examples of the quaternary alkyl ammonium include trimethylstearyl ammonium, dimethylstearylbenzyl ammonium, dimethyloctadecyl ammonium, and oleylbis(2-hydroxyethyl)methyl ammonium.
[0097] Examples of the modified layered inorganic minerals include BENTONE34, BENTONE52, BENTONE38, BENTONE27, BENTONE57, BENTONE SD1, BENTONE SD2, and BENTONE SD3 manufactured by ELEMENTIS Co., Ltd.; CRAYTONE34, CRAYTONE40, CRAYTONE HT, CRAYTONE2000, CRAYTONE AF, CRAYTONE APA, and CRAYTONE HY manufactured by SCP Co., Ltd.; Sben, Sben E, Sben C, Sben NZ, Sben NZ70, Sben W, Sben N400, Sben NX, Sben NX80, Sben NO12S, Sben NEZ, Sben NO12, Sben WX, and Sben NE manufactured by HOJUN Co., Ltd.; and KUNIVIS110, KUNIVIS120, and KUNIVIS127 manufactured by Kunimine Kogyo Co., Ltd.
[0098] The modified layered inorganic mineral and binder resin kneaded composite, i.e., master batch, can be obtained by mixing and kneading the modified layered inorganic mineral with the binder resin under high shear force. In this case, an organic solvent can be used to enhance the interaction between the modified layered inorganic mineral and the binder resin.
[0099] In addition, the so-called flushing method, in which an aqueous paste containing the modified layered inorganic mineral and water is mixed and kneaded with a resin and an organic solvent, the modified layered inorganic mineral is transferred to the resin side, and the water and organic solvent components are removed, is also preferably used because the wet cake can be used as is and does not need to be dried. A high-shear dispersing device such as a three-roll mill is preferably used for mixing and kneading.
[0100] In the kneaded composite of the modified layered inorganic mineral and the binder resin, i.e., in the master batch, it is desirable that the average dispersed particle size of the modified layered inorganic mineral is 0.1 μm to 0.55 μm, and the frequency of the modified layered inorganic mineral having a volume average particle size of 1 μm or more is 15% or less. If the average dispersed particle size exceeds 0.55 μm or the frequency of particles having a particle size of 1 μm or more exceeds 15%, the effect on the toner shape and the toner charging performance tends to decrease.
[0101] The modified layered inorganic mineral is preferably contained in the toner in an amount of 0.1% by mass to 1.4% by mass, more preferably 0.5% by mass to 1.0% by mass. If the amount is less than 0.1% by mass, the effect on the toner shape and the toner charging performance is reduced, and if the amount is more than 1.4% by mass, the fixing performance is deteriorated.
[0102] -External additives- The external additive is not particularly limited and can be appropriately selected according to the purpose. Examples of the external additive include various inorganic fine particles and hydrophobized inorganic fine particles. In addition, fatty acid metal salts (e.g., zinc stearate, aluminum stearate, etc.) and fluoropolymers can also be used.
[0103] Examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, silicon nitride, etc. Among these, silica and titanium dioxide are particularly preferred.
[0104] Suitable additives include hydrophobized silica, titania, titanium oxide, and alumina fine particles. Examples of silica fine particles include R972, R974, RX200, RY200, R202, R805, and R812 (all manufactured by Nippon Aerosil Co., Ltd.). Examples of titania fine particles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, and STT-65C-S (all manufactured by Titanium Industries Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Industries Co., Ltd.), MT-150W, MT-500B, MT-600B, and MT-150A (all manufactured by Teika Co., Ltd.).
[0105] Examples of hydrophobically treated titanium oxide particles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-500T, TAF-1500T (all manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-100S, MT-100T (all manufactured by Teika Co., Ltd.), and IT-S (manufactured by Ishihara Sangyo Kaisha, Ltd.).
[0106] Hydrophobized oxide particles, hydrophobized silica particles, hydrophobized titania particles, and hydrophobized alumina particles can be obtained by treating hydrophilic particles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, octyltrimethoxysilane, etc. Silicone oil-treated oxide particles and inorganic particles, which are treated with silicone oil by heating as necessary, are also suitable.
[0107] Examples of the silicone oil include dimethyl silicone oil, methylphenyl silicone oil, chlorophenyl silicone oil, methylhydrogen silicone oil, alkyl-modified silicone oil, fluorine-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, epoxy-polyether-modified silicone oil, phenol-modified silicone oil, carboxyl-modified silicone oil, mercapto-modified silicone oil, methacryl-modified silicone oil, and α-methylstyrene-modified silicone oil.
[0108] The average particle size of the primary particles of the inorganic fine particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 100 nm or less, more preferably 3 to 70 nm. If it is smaller than 3 nm, the inorganic fine particles are embedded in the toner and are unlikely to effectively exert their function. If it is larger than 100 nm, it is not preferable because it will damage the photoreceptor surface unevenly.
[0109] The average particle size of the primary particles of the hydrophobized inorganic fine particles is preferably 1 nm to 100 nm, more preferably 5 nm to 70 nm. It is also preferable that the hydrophobized inorganic fine particles contain at least one type of inorganic fine particles having an average particle size of 20 nm or less, and at least one type of inorganic fine particles having an average particle size of 30 nm or more. The specific surface area by the BET method is 20 m 2 / g or more 500m 2 It is preferable that the molecular weight is not more than 1 / g.
[0110] The content of the external additive is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 parts by mass to 5 parts by mass, more preferably 0.3 parts by mass to 3 parts by mass, relative to 100 parts by mass of the toner.
[0111] -Flow improver- The flowability improver is not particularly limited as long as it can improve hydrophobicity by surface treatment and prevent deterioration of flowability and charging property even under high humidity, and can be appropriately selected according to purpose.Examples thereof include silane coupling agent, silylating agent, silane coupling agent with fluorinated alkyl group, organic titanate coupling agent, aluminum coupling agent, silicone oil, modified silicone oil, etc.The silica and titanium oxide are particularly preferably surface-treated with such flowability improver and used as hydrophobic silica and hydrophobic titanium oxide.
[0112] -Cleaning improver- The cleaning property improver is added to the toner to remove the developer remaining on the photoconductor or the primary transfer medium after transfer, and is not particularly limited and can be appropriately selected according to the purpose. Examples include zinc stearate, calcium stearate, fatty acid metal salts such as stearic acid, polymethyl methacrylate fine particles, polystyrene fine particles, and other polymer fine particles produced by soap-free emulsion polymerization. The polymer fine particles preferably have a relatively narrow particle size distribution, and are preferably 0.01 to 1 μm in volume average particle size.
[0113] -Magnetic materials- The magnetic material is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include iron powder, magnetite, ferrite, etc. Among these, those that are white in color are preferred.
[0114] <Glass transition temperature (Tg1st)> The glass transition temperature (Tg1st) of the toner of the present invention at the first temperature rise in differential scanning calorimetry (DSC) is 45° C. or more and 65° C. or less, and preferably 50° C. or more and 60° C. or less. If the Tg is less than 45° C., the toner is likely to aggregate due to temperature changes during transportation and storage of the toner in summer or tropical regions. As a result, solidification in the toner bottle and toner adhesion in the developing machine occur. In addition, poor supply due to toner clogging in the toner bottle and image abnormalities due to toner adhesion in the developing machine tend to occur. If the Tg is greater than 65° C., good low-temperature fixability cannot be obtained.
[0115] The glass transition temperatures (Tga1st and Tgb1st) in the first heating run of the DSC of the toner of the present invention can be adjusted to a desired range by changing the composition ratio of the aliphatic diol and the dicarboxylic acid component of polyester resin A, the glass transition temperature of polyester resin B, the glass transition temperature of polyester resin C, and the composition ratios of polyester resin A, polyester resin B and polyester resin C.
[0116] <Mass average particle diameter D4, mass average particle diameter D4 / number average particle diameter Dn> The mass average particle diameter D4 of the toner is, for example, preferably from 3 μm to 7 μm, and more preferably from 4 μm to 6 μm. By making the volume average particle diameter 3 μm or more, even in a two-component developer, it is possible to suppress the toner from fusing to the surface of the carrier due to long-term stirring in the developing device, and to prevent the charge ability of the carrier from decreasing. Also, by making the volume average particle diameter 7 μm or less, it is possible to obtain a high-resolution, high-quality image. Furthermore, it is possible to reduce the variation in the particle diameter of the toner when the toner balance in the developer is performed.
[0117] The ratio D4 / Dn of the mass average particle diameter D4 to the number average particle diameter Dn is preferably 1.00 or more and 1.20 or less, and more preferably 1.10 or more and 1.18 or less. The mass average particle diameter (D4) and number average particle diameter (Dn) of the toner, as well as their ratio (D4 / Dn), were measured using a particle size measuring device (Multisizer III, manufactured by Beckman Coulter) with an aperture diameter of 100 μm, and analyzed using analysis software (Beckman Coulter Multisizer3 Version 3.51).
[0118] Specifically, 0.5 mL of 10% by weight surfactant (alkylbenzene sulfonate NEOGEN SC-A; manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to a 100 mL glass beaker, 0.5 g of each toner was added, and the mixture was stirred with a micro spatula, and then 80 mL of ion-exchanged water was added. The resulting dispersion was dispersed for 10 minutes using an ultrasonic disperser (W-113MK-II, manufactured by Honda Electronics Co., Ltd.). The dispersion was measured using the Multisizer III and Isoton III (manufactured by Beckman Coulter) as the measurement solution. The toner sample dispersion was dropped so that the concentration indicated by the device was 8±2%.
[0119] <Average circularity> The average circularity is a value obtained by dividing the perimeter of a circle having the same projected area as the shape of the toner by the perimeter of an actual particle, and is, for example, preferably 0.95 to 0.99, more preferably 0.96 to 0.98. When the average circularity is 0.95 or more, a high-quality image with satisfactory transferability and no dust can be obtained. When the average circularity is 0.99 or less, the cleaning property can be improved, and a high-quality image can be obtained. That is, in an image forming system employing blade cleaning or the like, the cleaning property of the photoconductor and the transfer belt is improved. Then, in the case of image formation with a high image area ratio such as a photographic image, the occurrence of background smearing of an image, which is caused by toner forming an image that has not been transferred due to poor paper feed or the like and accumulated as a transferred image on the photoconductor, can be suppressed. Also, the contamination of the charging roller that contact-charges the photoconductor can be suppressed, and the original charging ability can be fully exhibited.
[0120] The average circularity was determined using a flow type particle image analyzer (FPIA-3000, manufactured by Sysmex Corporation). Using a container from which impurity solids had been removed in advance, 0.1 mL to 0.5 mL of alkylbenzene sulfonate was added as a dispersant to 100 mL to 150 mL of water, and approximately 0.1 g to 0.5 g of toner was further added. The suspension in which the sample was dispersed was subjected to a dispersion treatment for approximately 1 to 3 minutes using an ultrasonic disperser, and the dispersion concentration was set to 3000 particles / μl to 10000 particles / μl, and the shape and distribution of the toner were measured using the above-mentioned device to obtain the average circularity.
[0121] <Silica release rate> It is preferable that the liberation rate A (mass %) of silica in the toner of the present invention satisfies the relationship of the following formula (1). 0.5≦A<1.0...Equation (1) The silica liberation rate of the toner of the present invention is more preferably 0.6% or more and less than 0.9%. If the silica liberation rate is less than 0.5%, the silica will be easily embedded in the toner, resulting in poor cleaning properties and the likelihood of streaky or band-like abnormal images. If the silica liberation rate exceeds 1.0%, the silica will be easily detached from the surface of the toner base, and the detached silica may contaminate the belt or photoreceptor.
[0122] <Silica release rate measurement using ultrasonic vibration method> In a 500 mL beaker, 10 g of polyoxyalkylene alkyl ether (Noigen ET-165, Daiichi Kogyo Seiyaku Co., Ltd.) and 300 mL of pure water were placed, and dispersed by ultrasonication for 1 hour to obtain Dispersion A. Dispersion A was then transferred to a 2 L measuring flask, diluted with the solution, and dissolved by ultrasonication for 1 hour to obtain Dispersion B containing 0.5% polyoxyalkylene alkyl ether.
[0123] 50 mL of dispersion B was poured into a 110 mL screw tube, and 3.75 g of sample toner was added. Dispersion C was obtained by stirring for 30 to 90 minutes until the screw tube was absorbed into dispersion B. At this time, the rotation was kept as low as possible to prevent bubbles from being generated. After the toner was sufficiently dispersed, the vibration part of an ultrasonic homogenizer (VCX750, manufactured by SONICS & Materials, Inc., 20 kHz, 750 watts) was inserted 2.5 cm into dispersion C, and ultrasonic vibration was applied for 1 minute at 40% output energy to produce dispersion D.
[0124] Dispersion D was placed in a 50 mL centrifuge tube and centrifuged at 2,000 rpm for 2 minutes to obtain a supernatant and a precipitate. The precipitate was poured into a separatory funnel while being washed with 60 mL of pure water, and the washing water was removed by suction filtration. The precipitate after filtration was placed in the mini cup again, 60 mL of pure water was poured into the mini cup, and the mixture was stirred five times with the handle of a spatula. Do not stir too vigorously. The washing water was again removed by suction filtration, and the toner remaining on the filter paper was collected and dried in a 40° C. thermostatic chamber for 8 hours.
[0125] After drying, 3 g of the toner obtained was molded into pellets having a diameter of 3 mm and a thickness of 2 mm using an automatic pressure molding machine (T-BRB-32, manufactured by Maekawa; load 6.0 t, pressure time 60 seconds), and treated to obtain sample toner. The initial sample toner that had not been subjected to the above treatment was similarly molded into pellets having a diameter of 3 mm and a thickness of 2 mm to prepare pre-treatment sample toner.
[0126] The amount of silica in the pelletized sample toner was measured by quantitative analysis using a fluorescent X-ray analyzer (ZSX-100e, manufactured by Rigaku Corporation). The calibration curve used was created in advance using sample toners with silica contents of 0.1, 1, and 1.8 parts per 100 parts of toner. The silica liberation rate (mass%) and the reduction amount (%) were calculated by the following formulas. Silica liberation rate A (mass%)=[Silica content of sample toner before treatment (parts)−Silica content of sample toner after treatment (parts)] / sample toner before treatment (parts)×100
[0127] <Methods of calculating and analyzing various characteristics of toner and toner components> Next, a method for calculating and analyzing various characteristics of the toner and toner components will be described. The glass transition temperature Tg, acid value, hydroxyl value, molecular weight, and melting point of the toner components such as the polyester resins A, B, and C, the crystalline polyester resin, and the release agent may be measured for each of them, or may be measured for each of the separated components after separation from the actual toner by Soxhlet extraction, gel permeation chromatography (GPC), etc. In the present invention, the means for separating the toner components in the toner can be selected arbitrarily, but the glass transition temperature Tg of the target sample is measured by the method described later.
[0128] First, an example will be described. An example of a method for measuring the glass transition temperature of each of polyester resin A, polyester resin B, and polyester resin C in a toner will be shown. 1 g of toner is placed in 100 mL of THF, and Soxhlet extraction is performed to obtain a THF-soluble fraction and an insoluble fraction. This is then dried for 24 hours in a vacuum dryer, and a mixture of polyester resin C and crystalline polyester resin is obtained from the THF-soluble fraction, and a mixture of polyester resin A and polyester resin B is obtained from the THF-insoluble fraction. These are used as target samples, and the glass transition temperatures are measured using the method described below.
[0129] In addition, since polyester resin A and polyester resin B have different glass transition temperatures, the glass transition temperatures of polyester resin A and polyester resin B can be determined by obtaining a mixture of polyester resin A and polyester resin B as described above and measuring the glass transition temperature of this mixture.
[0130] Next, other examples will be described. 1 g of toner is put into 100 mL of THF, and the solution is obtained by stirring for 30 minutes under a condition of 25°C, in which the soluble portion is dissolved. This is filtered through a membrane filter with an opening of 0.2 μm to obtain the THF-soluble portion in the toner. Next, this is dissolved in THF to prepare a sample for GPC measurement, and is injected into a GPC used to measure the molecular weight of polyester resin C. In addition, the THF-insoluble portion in the toner is used as a sample for GPC measurement as a sample for measurement of polyester resin A and polyester resin B.
[0131] On the other hand, a fraction collector is placed at the eluate outlet of the GPC, and the eluate is fractionated at a predetermined count, and the eluate is obtained at 5% area ratios from the start of elution (the rise of the curve) of the elution curve. Next, for each elution, 30 mg of sample is dissolved in 1 mL of deuterated chloroform, and 0.05 vol% of tetramethylsilane (TMS) is added as a reference substance. The eluate is filled into a 5 mm diameter glass tube for NMR measurement, and a nuclear magnetic resonance device (JNM-AL400 manufactured by JEOL Ltd.) is used to perform 128 integrations at 23°C to 25°C to obtain a spectrum. The monomer composition and composition ratio of polyester resins A, B, C, crystalline polyester resin, etc. contained in the toner can be obtained from the peak integral ratio of the obtained spectrum.
[0132] Next, an example of separation of each component by GPC will be described. In GPC measurement using THF as the mobile phase, the eluate is fractionated using a fraction collector or the like, and fractions corresponding to the desired molecular weight portion of the full integral of the elution curve are collected. Next, the collected eluate is concentrated and dried using an evaporator or the like, and the solid content is dissolved in a heavy solvent such as deuterated chloroform or deuterated THF, and 1H-NMR measurement is performed to calculate the constituent monomer ratio of the resin in the eluted component from the integral ratio of each element. As another method, the eluate may be concentrated, hydrolyzed with sodium hydroxide or the like, and the decomposition product may be qualitatively and quantitatively analyzed by high performance liquid chromatography (HPLC) or the like to calculate the constituent monomer ratio.
[0133] In addition, in the case where the toner manufacturing method forms toner base particles while generating a polyester resin by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, the polyester resin may be separated from the actual toner by GPC or the like to determine the Tg and other properties of the polyester resin, or a polyester resin may be synthesized separately by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, and the Tg and other properties of the synthesized polyester resin may be measured.
[0134] <<Measuring method for melting point and glass transition temperature Tg>> The melting point and glass transition temperature Tg in the present invention are measured using a DSC system (differential scanning calorimeter) ("Q-200", manufactured by TA Instruments). Specifically, the melting point and glass transition temperature of the sample are measured according to the following procedure.
[0135] First, about 5.0 mg of the target sample is placed in an aluminum sample container, the sample container is placed on a holder unit, and set in an electric furnace. Next, in a nitrogen atmosphere, the sample is heated from -80°C to 150°C at a heating rate of 10°C / min (first heating). After that, the sample is cooled from 150°C to -80°C at a heating rate of 10°C / min, and further heated to 150°C at a heating rate of 10°C / min (second heating). During each of the first and second heating, a DSC curve is measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments).
[0136] From the obtained DSC curves, the analysis program in the Q-200 system can be used to select the DSC curve at the first heating and determine the glass transition temperature Tg1st of the target sample at the first heating. Similarly, the DSC curve at the second heating can be selected and the glass transition temperature Tg2nd of the target sample at the second heating can be determined.
[0137] In the present invention, the obtained DSC curve is analyzed using an analysis program in the Q-200 system, with "Reversing Heat Flow" plotted on the vertical axis to obtain a DSC curve as shown in FIG. 1, and the onset value shown in FIG. 1 is taken as the Tg in the present invention. In addition, this measurement is preferably performed by raising the temperature by applying a modulation temperature amplitude as shown below, since the glass transition temperature of the first temperature rise can be separated into two points, Tga1st and Tgb1st, for the THF-insoluble component of the toner.
[0138] (Measurement conditions) Using the modulation mode, heat from -80°C to 150°C at a heating rate of 1.0°C / min with a modulation temperature amplitude of ±1.0°C / min (first heating), then cool from 150°C to -80°C at a temperature drop rate of 10°C / min, and further heat to 150°C at a heating rate of 1.0°C / min (second heating). The obtained DSC curve was obtained by plotting "Reversing Heat Flow" on the vertical axis using the analysis program in the Q-200 system in the same manner as above, and the onset value shown in FIG. 1 was taken as the Tg of the present invention.
[0139] Furthermore, from the obtained DSC curves, the analysis program in the Q-200 system can be used to select the DSC curve during the first heating and determine the endothermic peak top temperature during the first heating of the target sample as the melting point. Similarly, the DSC curve during the second heating can be selected and the endothermic peak top temperature during the second heating of the target sample as the melting point. Unless otherwise specified, the melting points and glass transition temperatures Tg of the polyester resins A, B, and C, the release agent, and other constituent components are the endothermic peak top temperature and glass transition temperature Tg2nd during the second heating, respectively, of each sample.
[0140] <Mass ratio of polyester resin> In the present invention, when the mass ratio of polyester resin A to the total mass of polyester resin A, polyester resin B, and polyester resin C is a, the mass ratio of polyester resin B is b, and the mass ratio of polyester resin C is c, it is preferable that the following relational formula (2) is satisfied. 4(a+b) <c ···(2)
[0141] By satisfying the above relational expression (2), separation of the resin can be prevented, and poor pigment dispersion and a decrease in coloring degree can be prevented. In addition, a good image can be obtained, and fixing area and storage stability can be ensured. In this embodiment, as described above, the mass ratio of the polyester resins can be determined by obtaining the combined product of polyester resins A and B, and the combined product of polyester resin C and the crystalline polyester resin in the toner by Soxhlet extraction, GPC, or the like, and then calculating the masses thereof.
[0142] <Toner manufacturing method> The method for producing the toner is not particularly limited and can be appropriately selected depending on the purpose. However, it is preferable to granulate the toner by dispersing an oil phase containing the polyester resins A, B, and C and, if necessary, the crystalline polyester resin, a release agent, a colorant, etc., in an aqueous medium.
[0143] Moreover, the polyester resins A and B contain a polyester resin which is a prepolymer having a urethane bond and / or a urea bond, and a polyester resin which does not have a urethane bond and / or a urea bond, preferably the crystalline polyester resin, and further preferably are granulated by dispersing an oil phase which contains the curing agent, release agent, colorant, etc., as necessary, in an aqueous medium.
[0144] As a method for producing such a toner, a known solution suspension method can be mentioned. As an example, a method of forming toner base particles while generating a polyester resin by an elongation reaction and / or a crosslinking reaction between the prepolymer and the curing agent will be described. In this method, an aqueous medium is prepared, an oil phase containing the toner materials is prepared, the toner materials are emulsified or dispersed, and the organic solvent is removed.
[0145] - Preparation of aqueous medium (aqueous phase) - The aqueous medium can be prepared, for example, by dispersing resin particles in the aqueous medium. The amount of the resin particles added to the aqueous medium is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5 to 10 parts by mass relative to 100 parts by mass of the aqueous medium.
[0146] The aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include water, a solvent miscible with water, and a mixture thereof. These may be used alone or in combination of two or more. Among these, water is preferred. The water-miscible solvent is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include alcohol, dimethylformamide, tetrahydrofuran, cellosolves, lower ketones, etc. Examples of the alcohol include methanol, isopropanol, ethylene glycol, etc. Examples of the lower ketones include acetone, methyl ethyl ketone, etc.
[0147] - Preparation of oil phase - In the present embodiment, the oil phase containing the toner materials can be prepared by dissolving or dispersing toner materials including polyester resins A and B, which are prepolymers having a urethane bond and / or a urea bond, and polyester resin C having no urethane bond and / or urea bond, and further including the crystalline polyester resin, a curing agent, a releasing agent, a colorant, and the like, as necessary, in an organic solvent. The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, but an organic solvent having a boiling point of less than 150° C. is preferred in terms of ease of removal.
[0148] Examples of the organic solvent having a boiling point of less than 150° C. include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, and methyl isobutyl ketone. These may be used alone or in combination of two or more. Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, carbon tetrachloride, etc. are preferable, and ethyl acetate is more preferable.
[0149] -Emulsification or dispersion- The toner materials can be emulsified or dispersed by dispersing an oil phase containing the toner materials in the aqueous medium, and when the toner materials are emulsified or dispersed, the curing agent and the prepolymer can undergo an elongation reaction and / or a crosslinking reaction.
[0150] The reaction conditions (reaction time, reaction temperature) for producing the prepolymer are not particularly limited and can be appropriately selected depending on the combination of the curing agent and the prepolymer. The reaction time is preferably 10 minutes to 40 hours, more preferably 2 hours to 24 hours. The reaction temperature is preferably 0°C to 150°C, more preferably 40°C to 98°C.
[0151] The step of uniformly dispersing the oil phase is not particularly limited, and a homomixer, a milder, or a bead mill can be appropriately selected depending on the oil phase formulation, the viscosity of the oil phase, etc. The dispersion time is preferably 1 hour to 5 hours, and more preferably 1 hour to 3 hours.
[0152] The method for stably forming a dispersion liquid containing the prepolymer in the aqueous medium is not particularly limited and can be appropriately selected depending on the purpose. For example, there is a method in which an oil phase prepared by dissolving or dispersing a toner material in a solvent is added to an aqueous medium phase, and the mixture is dispersed by shear force.
[0153] The dispersing machine for the dispersion is not particularly limited and can be appropriately selected according to the purpose. For example, low-speed shear dispersing machine, high-speed shear dispersing machine, friction dispersing machine, high-pressure jet dispersing machine, ultrasonic dispersing machine, etc. can be mentioned. Among these, high-speed shear dispersing machine is preferable because it can control the particle size of the dispersion (oil droplets) to 2 μm to 20 μm.
[0154] When using the high-speed shear type disperser, the conditions such as the rotation speed, dispersion time, and dispersion temperature can be appropriately selected depending on the purpose. The rotation speed is preferably 1,000 rpm to 30,000 rpm, and more preferably 5,000 rpm to 20,000 rpm. In the case of a batch method, the dispersion time is preferably 0.1 minutes to 5 minutes. The dispersion temperature is preferably 0°C to 150°C under pressure, and more preferably 40°C to 98°C. Generally, the higher the dispersion temperature, the easier the dispersion.
[0155] The amount of the aqueous medium used when emulsifying or dispersing the toner materials is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50 parts by mass or more and 2,000 parts by mass or less, and more preferably 100 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of the toner materials. By using an aqueous medium of 50 parts by mass or more, the dispersion state of the toner materials becomes good, and toner base particles of a predetermined particle size can be obtained. In addition, by using an aqueous medium of 2,000 parts by mass or less, the production cost does not increase.
[0156] When the oil phase containing the toner materials is emulsified or dispersed, it is preferable to use a dispersant from the viewpoints of stabilizing the dispersion such as oil droplets, forming a desired shape, and sharpening the particle size distribution. The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include surfactants, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. These may be used alone or in combination of two or more. Among these, surfactants are preferred.
[0157] The surfactant is not particularly limited and can be appropriately selected depending on the purpose, and for example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, etc. can be used. Examples of the anionic surfactant include alkylbenzene sulfonates, α-olefin sulfonates, and phosphate esters. Among these, those having a fluoroalkyl group are preferred.
[0158] -Removal of organic solvents- The method for removing the organic solvent from the dispersion liquid such as the emulsified slurry is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include a method in which the temperature of the entire reaction system is gradually increased to evaporate the organic solvent in the oil droplets, and a method in which the dispersion liquid is sprayed in a dry atmosphere to remove the organic solvent in the oil droplets.
[0159] When the organic solvent is removed, toner base particles are formed. The toner base particles can be washed, dried, etc., and can further be classified, etc. The classification can be performed by removing fine particles in a liquid using a cyclone, decanter, centrifugal separation, etc., or the classification operation can be performed after drying.
[0160] The obtained toner base particles may be mixed with particles of the external additive, the charge control agent, etc. At this time, by applying a mechanical impact force, it is possible to suppress the particles of the external additive, etc. from being detached from the surface of the toner base particles.
[0161] The method of applying the mechanical impact force is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include a method of applying an impact force to the mixture using a blade rotating at high speed, a method of introducing the mixture into a high-speed air stream and accelerating it to collide the particles with each other or with a suitable collision plate, etc. The apparatus used in the above method is not particularly limited and can be appropriately selected depending on the purpose. Examples include Angmill (manufactured by Hosokawa Micron Corporation), an apparatus obtained by modifying I-type mill (manufactured by Japan Pneumatic Co., Ltd.) to reduce the grinding air pressure, Hybridization System (manufactured by Nara Machinery Works), Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), and automatic mortar.
[0162] (Developer) The developer of the present invention contains at least the toner of the present invention, and contains other components such as a carrier, which are appropriately selected as necessary. Therefore, it has excellent transferability, chargeability, etc., and can stably form high-quality images. The developer may be a one-component developer or a two-component developer, but when used in a high-speed printer that corresponds to the recent improvement in information processing speed, a two-component developer is preferred because it has an improved life.
[0163] When the developer is used as a one-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, there is little filming of the toner on the developing roller, and there is little melting of the toner to components such as blades that thin the toner layer, and good and stable developability and images can be obtained even with long-term stirring in the developing device.
[0164] When the developer is used as a two-component developer, even if the toner is balanced over a long period of time, the particle size of the toner does not vary much, and good and stable developability and images can be obtained even with long-term stirring in a developing device.
[0165] (Two-component developer carrier) When the toner of the present invention is used in a two-component developer, it may be mixed with a magnetic carrier, and the content ratio of the carrier and the toner in the developer is preferably 1 to 10 parts by mass of the toner per 100 parts by mass of the carrier. As the magnetic carrier, conventionally known ones having a particle diameter of about 20 to 200 μm, such as iron powder, ferrite powder, magnetite powder, and magnetic resin carriers, can be used. In addition, as the coating material, amino resins such as urea-formaldehyde resins, melamine resins, benzoguanamine resins, urea resins, polyamide resins, and epoxy resins can be used. Also usable are polyvinyl and polyvinylidene resins, such as acrylic resins, polymethyl methacrylate resins, polyacrylonitrile resins, polyvinyl acetate resins, polyvinyl alcohol resins, polyvinyl butyral resins, polystyrene resins and styrene-acrylic copolymer resins, halogenated olefin resins such as polyvinyl chloride, polyester resins such as polyethylene terephthalate resins and polybutylene terephthalate resins, polycarbonate resins, polyethylene resins, polyvinyl fluoride resins, polyvinylidene fluoride resins, polytrifluoroethylene resins, polyhexafluoropropylene resins, copolymers of vinylidene fluoride and acrylic monomers, copolymers of vinylidene fluoride and vinyl fluoride, fluoro terpolymers such as terpolymers of tetrafluoroethylene, vinylidene fluoride and non-fluorinated monomers, and silicone resins. Also, conductive powders and the like may be contained in the coating resin as necessary. As conductive powders, metal powders, carbon black, titanium oxide, tin oxide, zinc oxide, and the like can be used. These conductive powders preferably have an average particle size of 1 μm or less. If the average particle size is greater than 1 μm, it becomes difficult to control the electrical resistance.
[0166] (Toner storage unit) The toner storage unit in the present invention refers to a unit having a function of storing toner and storing the toner. Examples of the toner storage unit include a toner storage container, a developing unit, and a process cartridge. The toner storage container refers to a container that stores toner. The developing device has a means for containing toner and developing the toner.
[0167] The process cartridge is a cartridge that integrates at least an electrostatic latent image carrier (also called an image carrier) and a developing means, contains toner, and is detachable from an image forming apparatus. The process cartridge may further include at least one selected from a charging means, an exposure means, and a cleaning means. By mounting the toner storage unit of the present invention on an image forming apparatus and forming an image, it is possible to form a high-definition, high-quality image while ensuring the brilliance of the image.
[0168] (Process cartridge) The developer of the present invention can be used in an image forming apparatus equipped with a process cartridge as shown in FIG. In the present invention, a plurality of components, such as a photosensitive member, a charging means, a developing means, and a cleaning means, are combined together to form a process cartridge, and this process cartridge is configured to be detachably attached to the main body of an image forming apparatus such as a copier or printer.
[0169] The process cartridge (71) shown in Figure 2 includes a photoconductor (72), charging means (73), developing means (74), and cleaning means (75). The operation of the process cartridge will be described below. First, the photoconductor (72) is rotated at a predetermined peripheral speed. During the rotation process, the photoconductor (72) is uniformly charged to a predetermined positive or negative potential on its peripheral surface by the charging means (73), and then receives image exposure light from an image exposure means such as a slit exposure or laser beam scanning exposure. In this way, an electrostatic latent image is sequentially formed on the peripheral surface of the photoconductor.
[0170] The electrostatic latent image thus formed is then developed with toner by the developing means (74). The developed toner images are then transferred by the transfer means to a transfer material fed from a paper feed section between the photoconductor and the transfer means in synchronization with the rotation of the photoconductor. The transfer material to which the image has been transferred is separated from the photoconductor surface and introduced into the image fixing means where the image is fixed, and is printed out as a duplicate (copy) outside the apparatus. After the image has been transferred, the surface of the photoconductor (72) is cleaned by the cleaning means (75) to remove any remaining toner, and is then neutralized before being used repeatedly for image formation.
[0171] (Image forming device) As an image forming apparatus for carrying out the image forming method of the present invention, for example, the image forming apparatuses shown in FIG. 3 and FIG. 4 can be used. 3, the main body (100) is mainly composed of image writing units (120Bk, 120C, 120M, 120Y) for forming color images by electrophotography, image forming units (130Bk, 130C, 130M, 130Y), and a paper feed unit (140). Based on the image signal, an image processing unit (not shown) performs image processing and converts it into color signals for black (Bk), cyan (C), magenta (M), and yellow (Y) for image formation, and sends them to the image writing units (120Bk, 120C, 120M, 120Y). The image writing units (120Bk, 120C, 120M, 120Y) are, for example, laser scanning optical systems consisting of a laser light source, a deflector such as a rotating polygon mirror, a scanning imaging optical system, and a group of mirrors (none of which are shown), and have four writing optical paths corresponding to each of the above-mentioned color signals, and perform image writing on the image forming units (130Bk, 130C, 130M, 130Y) according to each color signal.
[0172] The image forming unit (130Bk, 130C, 130M, 130Y) is equipped with photoconductors (210Bk, 210C, 210M, 210Y) for black, cyan, magenta, and yellow, respectively, and OPC photoconductors are normally used for these photoconductors (210Bk, 210C, 210M, 210Y) for each color. Around each photoconductor (210Bk, 210C, 210M, 210Y), there are arranged a charging device (215Bk, 215C, 215M, 215Y), a laser light exposure section from the image writing section (120Bk, 120C, 120M, 120Y), a developing device for each color (200Bk, 200C, 200M, 200Y), a primary transfer device (230Bk, 230C, 230M, 230Y), a cleaning device (300Bk, 300C, 300M, 300Y), a charge removing device (not shown), etc. The developing devices (200Bk, 200C, 200M, 200Y) use a two-component magnetic brush development method. In addition, an intermediate transfer belt (220) is interposed between each photoconductor (210Bk, 210C, 210M, 210Y) and the primary transfer device (230Bk, 230C, 230M, 230Y), and the toner images of each color are transferred from each photoconductor in succession, superimposed on top of each other, onto this intermediate transfer belt (220), which carries the toner images on each photoconductor.
[0173] In some cases, it is preferable to provide a pre-transfer charger (502) as a pre-transfer charging means outside the intermediate transfer belt (220) at a position after the final color passes the primary transfer position and before the secondary transfer position. This pre-transfer charger (502) uniformly charges the toner image on the intermediate transfer belt (220) to the same polarity as the toner image before the toner image on the intermediate transfer belt (220) transferred to the photoconductor (210) in the primary transfer section is transferred to transfer paper as a transfer material.
[0174] The toner images on the intermediate transfer belt (220) transferred from each photoconductor (210Bk, 210C, 210M, 210Y) may have varying amounts of charge because they include halftone and solid areas and areas with different amounts of toner overlap. In addition, due to peeling discharge occurring in the gap adjacent to the primary transfer section downstream in the movement direction of the intermediate transfer belt, variations in the amount of charge may occur in the toner images on the intermediate transfer belt (220) after the primary transfer. Such variations in the amount of charge within the same toner image reduce the transfer margin in the secondary transfer section that transfers the toner image on the intermediate transfer belt (220) to the transfer paper. Therefore, the pre-transfer charger (502) uniformly charges the toner image before it is transferred to the transfer paper to the same polarity as the toner image, thereby eliminating the variations in the amount of charge within the same toner image and improving the transfer margin in the secondary transfer section.
[0175] As described above, according to this embodiment, the toner images on the intermediate transfer belt (220) transferred from the respective photoconductors (210Bk, 210C, 210M, 210Y) are uniformly charged by the pre-transfer charger (502), so that even if there is variation in the amount of charge in the toner image on the intermediate transfer belt (220), the transfer characteristics in the secondary transfer section can be made almost constant across each portion of the toner image on the intermediate transfer belt (220). Therefore, the decrease in the transfer margin when transferring to the transfer paper is suppressed, and the toner image can be stably transferred.
[0176] In the above embodiment, the amount of charge applied by the pre-transfer charger (502) varies depending on the moving speed of the intermediate transfer belt (220) which is the object to be charged. For example, if the moving speed of the intermediate transfer belt (220) is slow, the same portion of the toner image on the intermediate transfer belt (220) takes a longer time to pass through the area charged by the pre-transfer charger (502), and the amount of charge increases. Conversely, if the moving speed of the intermediate transfer belt (220) is fast, the amount of charge on the toner image on the intermediate transfer belt (220) decreases. Therefore, if the moving speed of the intermediate transfer belt (220) changes while the toner image on the intermediate transfer belt (220) is passing through the charging position by the pre-transfer charger (502), it is desirable to control the pre-transfer charger (502) according to the moving speed of the intermediate transfer belt (220) so that the amount of charge on the toner image does not change midway.
[0177] The pre-transfer charger (502) also includes a discharge wire (502a), a grid electrode (502b) interposed between the discharge wire (502a) and the intermediate transfer belt (220), and a casing (502c) made of a conductive material surrounding the discharge wire (502a). A high DC voltage of the same polarity as the charging polarity of the toner image on the intermediate transfer belt (220) is applied to the discharge wire (502a) by a power supply (803) for the pre-transfer charger (502), causing a corona discharge.
[0178] Conductive rollers (241), (242), and (243) are provided between the primary transfer devices (230Bk, 230C, 230M, and 230Y). After the transfer paper is fed from the paper feed section (140), it is carried on the transfer belt (500) via a pair of registration rollers (160), and where the intermediate transfer belt (220) and the transfer belt (500) come into contact with each other, the toner image on the intermediate transfer belt (220) is transferred to the transfer paper by the secondary transfer roller (600), thereby forming a color image.
[0179] After the image is formed, the transfer paper is transported by the transfer belt (500) to the fixing device (150), where the image is fixed to obtain a color image. Any toner remaining on the intermediate transfer belt (220) that has not been transferred is removed from the belt by the intermediate transfer belt cleaning device (260).
[0180] Since the polarity of the toner on the intermediate transfer belt (220) before transfer to the transfer paper is the same negative polarity as during development, a positive transfer bias voltage is applied to the secondary transfer roller (600) and the toner is transferred onto the transfer paper. The nip pressure at this point affects the transferability and significantly affects the fixing ability. In addition, the toner remaining on the intermediate transfer belt (220) that has not been transferred is discharged to the positive polarity side the moment the transfer paper and the intermediate transfer belt (220) separate, and is charged to the 0 to positive side. Note that when the transfer paper is jammed or a toner image formed in a non-image area is not affected by the secondary transfer, it naturally remains negative polarity.
[0181] The thickness of the photoconductor layer is 30 μm, the beam spot diameter of the optical system is 50 × 60 μm, and the light amount is 0.47 mW. The development process is performed with the photoconductor (black) (210Bk) charged (exposed side) potential V0 at -700 V, the post-exposure potential VL at -120 V, and the development bias voltage at -470 V, i.e., the development potential at 350 V. The toner (black) image formed on the photoconductor (black) (210Bk) is then transferred (to intermediate transfer belt and transfer paper) and fixed to form a completed image. First, all colors are transferred from the primary transfer device (230Bk, 230C, 230M, 230Y) to the intermediate transfer belt (220), and then transferred to the transfer paper by applying a bias to another secondary transfer roller (600).
[0182] The positively charged toner remaining on the intermediate transfer belt (220) is cleaned by the conductive fur brush (262) to which a negative voltage is applied. The method of applying a voltage to the conductive fur brush (262) is exactly the same as that of the conductive fur brush (261), except for the polarity. Most of the toner that was not transferred and remains is also cleaned by the two conductive fur brushes (261) and (262). Here, the toner, paper powder, talc, etc. that were not cleaned by the conductive fur brush (262) are negatively charged by the negative voltage of the conductive fur brush (262). The next primary transfer of black is a transfer using a positive voltage, and the negatively charged toner, etc. is attracted to the intermediate transfer belt (220), preventing it from migrating to the photoconductor (black) (210Bk) side.
[0183] Figure 4 shows another example of an image forming apparatus in which the image forming method of the present invention is implemented, which is a tandem-type indirect transfer electrophotographic apparatus. In the figure, (100) is the copying machine main body, (200) is the paper feed table on which it is placed, (300) is the scanner mounted on the copying machine main body (100), and (400) is the automatic document feeder (ADF) mounted on top of that. An endless belt-like intermediate transfer body (10) is provided in the center of the copying machine main body (100). As shown in FIG. 4, the intermediate transfer body (10) is wrapped around three support rollers (14), (15), and (16) in the illustrated example, and can be rotated and conveyed clockwise in the figure.
[0184] In this illustrated example, an intermediate transfer body cleaning device (17) is provided to the left of the second support roller (15) of the three, for removing residual toner remaining on the intermediate transfer body (10) after image transfer. Among the three, the intermediate transfer body (10) is stretched between the first support roller (14) and the second support roller (15), and four image forming means (18) for yellow, cyan, magenta, and black are arranged side by side along the transport direction on the intermediate transfer body (10) to form a tandem image forming device (20).
[0185] As shown in Fig. 4, an exposure device (21) is further provided above the tandem image forming device (20). Meanwhile, a secondary transfer device (22) is provided on the opposite side of the intermediate transfer body (10) from the tandem image forming device (20). In the illustrated example, the secondary transfer device (22) is configured by stretching an endless belt, a secondary transfer belt (24), between two rollers (23) and is positioned so as to be pressed against a third support roller (16) via the intermediate transfer body (10), and transfers the image on the intermediate transfer body (10) to a sheet. A fixing device (25) that fixes the transferred image on the sheet is provided next to the secondary transfer device (22). The fixing device (25) is configured by pressing a pressure roller (27) against a fixing belt (26), which is an endless belt.
[0186] The above-mentioned secondary transfer device (22) also has a sheet transport function for transporting the sheet after image transfer to this fixing device (25). Of course, a transfer roller or a non-contact charger may be disposed as the secondary transfer device (22), but in that case, it becomes difficult to also provide this sheet transport function. In the illustrated example, below the secondary transfer device (22) and the fixing device (25), a sheet inverting device (28) is provided in parallel with the above-mentioned tandem image forming device (20) to invert the sheet to record images on both sides of the sheet.
[0187] Now, when making a copy using this color electrophotographic apparatus, an original is set on the original table (30) of the automatic original feeder (400), or the automatic original feeder (400) is opened and an original is set on the contact glass (32) of the scanner (300), and the automatic original feeder (400) is closed to hold the original down. When a start switch (not shown) is pressed, if an original is set on the automatic original feeder (400), the original is fed and moved onto the contact glass (32), and if an original is set on the contact glass (32), the scanner (300) is immediately driven to travel the first traveling body (33) and the second traveling body (34). Then, light is emitted from the light source on the first traveling body (33), and the reflected light from the original surface is further reflected toward the second traveling body (34), reflected by the mirror of the second traveling body (34), and enters the reading sensor (36) through the imaging lens (35), and the contents of the original are read.
[0188] Furthermore, when a start switch (not shown) is pressed, a drive motor (not shown) drives and rotates one of the support rollers (14), (15), (16), which in turn rotates the other two support rollers, thereby rotating and transporting the intermediate transfer body (10). At the same time, each image forming means (18) rotates its photoconductor (40) to form monochrome images of black, yellow, magenta, and cyan on each photoconductor (40), respectively. Then, as the intermediate transfer body (10) is transported, these monochrome images are transferred in sequence to form a composite color image on the intermediate transfer body (10). On the other hand, when a start switch (not shown) is pressed, one of the paper feed rollers (42) of the paper feed table (200) is selected and rotated, and a sheet is fed from one of the paper feed cassettes (44) provided in multiple stages in the paper bank (43). The sheets are separated one by one by a separation roller (45) and placed in a paper feed path (46), and are transported by a transport roller (47) to a paper feed path (48) inside the copying machine main body (100), where they are stopped by a registration roller (49). Alternatively, the sheet feed roller (50) is rotated to feed the sheets on the manual feed tray (51), which are separated one by one by the separation roller (52) and fed into the manual feed path (53), where they are stopped by being struck against the registration rollers (49). Then, the registration roller (49) is rotated in time with the composite color image on the intermediate transfer body (10), and a sheet is fed between the intermediate transfer body (10) and the secondary transfer device (22), and the color image is transferred by the secondary transfer device (22) and recorded on the sheet.
[0189] The sheet after the image transfer is transported by the secondary transfer device (22) and sent to the fixing device (25), where the transferred image is fixed by applying heat and pressure, and then the sheet is switched by the switching claw (55) and discharged by the discharge rollers (56) and stacked on the paper output tray (57). Alternatively, the sheet is switched by the switching claw (55) and fed into the sheet inverting device (28), where it is inverted and guided to the transfer position again, an image is also recorded on the back side, and then the sheet is discharged by the discharge rollers (56) onto the paper output tray (57). Meanwhile, after the image transfer, the intermediate transfer body (10) is cleaned by an intermediate transfer body cleaning device (17) to remove any residual toner remaining on the intermediate transfer body (10) after the image transfer, in preparation for next image formation by the tandem image forming device (20). Here, the registration roller (49) is generally grounded when used, but it is also possible to apply a bias to it in order to remove paper dust from the sheet. EXAMPLES
[0190] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples. In the examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0191] The "prepolymer" synthesized below is the raw material for the "polyester resin," and in the toner manufacturing process, the "prepolymer" becomes the "polyester resin," which exists in the toner as the "polyester resin." The mass ratios a, b, and c of the polyester resin components described above are calculated by analyzing the toner, as described below.
[0192] (Manufacturing example A-1) <Synthesis of Prepolymer A-1> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 40 mol% isophthalic acid and 60 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-1]. Next, [Intermediate polyester A-1] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-1].
[0193] (Manufacturing example A-2) <Synthesis of prepolymer A-2> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 33 mol% isophthalic acid and 67 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-2]. Next, [Intermediate polyester A-2] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-2].
[0194] (Manufacturing example A-3) <Synthesis of prepolymer A-3> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 67 mol% isophthalic acid and 33 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-3]. Next, into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, [Intermediate Polyester A-3] and isophorone diisocyanate (IPDI) were added in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-3].
[0195] (Manufacturing example A-4) <Synthesis of prepolymer A-4> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 30 mol% isophthalic acid and 70 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-4]. Next, [Intermediate polyester A-4] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-4].
[0196] (Manufacturing example A-5) <Synthesis of prepolymer A-5> Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 70 mol% isophthalic acid and 30 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%. Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. Thereafter, the mixture was further reacted for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester A-5]. Next, [Intermediate polyester A-5] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [Prepolymer A-5].
[0197] (Manufacturing example B-1) <Synthesis of prepolymer B-1> In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 2 mol ethylene oxide adduct of bisphenol A, 2 mol propylene oxide adduct of bisphenol A, terephthalic acid and adipic acid were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.1, the composition of the diol component was 80 mol% of 2 mol ethylene oxide adduct of bisphenol A, 20 mol% of 2 mol propylene oxide adduct of bisphenol A, and the composition of the dicarboxylic acid component was 60 mol% of terephthalic acid and 40 mol% of adipic acid. After that, the temperature was raised to 200°C in about 4 hours, and then raised to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester B-1]. Next, the obtained [intermediate polyester B-1] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [prepolymer B-1].
[0198] (Manufacturing example B-2) <Synthesis of prepolymer B-2> In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, ethylene oxide 2 moles of bisphenol A, propylene oxide 2 moles of bisphenol A, terephthalic acid and adipic acid were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.1, the composition of the diol component was 80 mol% of ethylene oxide 2 moles of bisphenol A, 20 mol% of propylene oxide 2 moles of bisphenol A, and the composition of the dicarboxylic acid component was 30 mol% of terephthalic acid and 70 mol% of adipic acid. After that, the temperature was raised to 200°C in about 4 hours, and then raised to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [intermediate polyester B-2]. Next, the obtained [intermediate polyester B-2] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [prepolymer B-2].
[0199] (Manufacturing example B-3) <Synthesis of prepolymer B-3> In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, ethylene oxide 2 moles of bisphenol A, propylene oxide 2 moles of bisphenol A, terephthalic acid and adipic acid were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.1, the composition of the diol component was 80 mol% of ethylene oxide 2 moles of bisphenol A, 20 mol% of propylene oxide 2 moles of bisphenol A, and the composition of the dicarboxylic acid component was 80 mol% of terephthalic acid and 20 mol% of adipic acid. After that, the temperature was raised to 200°C in about 4 hours, and then raised to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg to obtain [Intermediate Polyester B-3]. Next, the obtained [intermediate polyester B-3] and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and after diluting with ethyl acetate to make a 50% ethyl acetate solution, the mixture was reacted at 100°C for 5 hours to obtain [prepolymer B-3].
[0200] (Manufacturing example C-1) <Synthesis of polyester resin C-1> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 75 / 25, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain [Polyester Resin C-1].
[0201] (Manufacturing example C-2) <Synthesis of polyester resin C-2> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 65 / 35, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain [Polyester Resin C-2].
[0202] (Manufacturing example C-3) <Synthesis of polyester resin C-3> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 85 / 15, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain [Polyester Resin C-3].
[0203] (Manufacturing example C-4) <Synthesis of polyester resin C-4> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 60 / 40, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain [Polyester Resin C-4].
[0204] (Manufacturing example C-5) <Synthesis of polyester resin C-5> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 90 / 10 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 75 / 25, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain [Polyester Resin C-5].
[0205] (Manufacturing example D-1) <Synthesis of crystalline polyester resin D-1> Dodecanedioic acid and 1,6-hexanediol were charged into a 5 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 0.9, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at 180°C for 10 hours, then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours to obtain [Crystalline Polyester Resin D-1].
[0206] <Preparation of Crystalline Polyester Resin Dispersion> A container equipped with a stirring rod and a thermometer was charged with 50 parts of [Crystalline Polyester Resin D-1] and 450 parts of ethyl acetate. The temperature was raised to 80 °C with stirring and held at 80 °C for 5 hours, then cooled to 30 °C in 1 hour. Using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.), dispersion was carried out under the conditions of a liquid feeding rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume filling of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain [Crystalline Polyester Resin Dispersion 1].
[0207] (Example 1) <Preparation of Masterbatch (MB)> 1,200 parts of water, 500 parts of carbon black (Printex 35 manufactured by Degussa) [DBP oil absorption = 42 mL / 100 mg, pH = 9.5], and 500 parts of [Polyester Resin C-1] were added and mixed with a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.). The mixture was kneaded at 150 °C for 30 minutes using two rolls, then rolled and cooled and pulverized with a pelletizer to obtain [Masterbatch 1].
[0208] <Preparation of WAX Dispersion> A container equipped with a stirring rod and a thermometer was charged with 50 parts of paraffin wax (manufactured by Nippon Seiro Co., Ltd., HNP-9, hydrocarbon wax, melting point 75 °C, SP value 8.8) as a mold release agent 1 and 450 parts of ethyl acetate. The temperature was raised to 80 °C with stirring and held at 80 °C for 5 hours, then cooled to 30 °C in 1 hour. Using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.), dispersion was carried out under the conditions of a liquid feeding rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume filling of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain [WAX Dispersion 1].
[0209] <Synthesis of Ketimine Compound> A reaction vessel equipped with a stirring rod and a thermometer was charged with 170 parts of isophoronediamine and 75 parts of methyl ethyl ketone, and the reaction was carried out at 50 °C for 5 hours to obtain [Ketimine Compound 1]. The amine value of [Ketimine Compound 1] was 418.
[0210] <Modified Layered Inorganic Mineral> The modified layered inorganic mineral used was "Clayton APA (manufactured by BYK Japan)."
[0211] <Preparation of oil phase> 500 parts of [WAX dispersion 1], 76 parts of [Prepolymer A-1], 152 parts of [Prepolymer B-1], 836 parts of [Polyester resin C-1], 100 parts of [Master batch 1], and 2 parts of [Ketimine compound 1] as a curing agent and 1.2 parts of [Modified layered inorganic mineral] were placed in a container and mixed at 5,000 rpm for 60 minutes using a TK Homomixer (manufactured by Primix Corporation). After that, a homogenization process was performed in which the mixture was further dispersed and homogenized using a bead mill to obtain [Oil phase 1].
[0212] <Synthesis of organic fine particle emulsion (fine particle dispersion)> In a reaction vessel equipped with a stirring rod and a thermometer, 683 parts of water, 11 parts of sodium salt of methacrylic acid ethylene oxide adduct sulfate (Eleminol RS-30: manufactured by Sanyo Chemical Industries, Ltd.), 138 parts of styrene, 138 parts of methacrylic acid, and 1 part of ammonium persulfate were charged and stirred at 400 rpm for 15 minutes, resulting in a white emulsion. The mixture was heated to a temperature of 75°C and reacted for 5 hours. Furthermore, 30 parts of 1% ammonium persulfate aqueous solution was added, and the mixture was aged at 75°C for 5 hours to obtain an aqueous dispersion of a vinyl resin (a copolymer of styrene-methacrylic acid-sodium salt of methacrylic acid ethylene oxide adduct sulfate) [fine particle dispersion 1]. The volume average particle diameter of [Fine Particle Dispersion 1] was measured to be 14 μm using an LA-920 (manufactured by Horiba, Ltd.) A part of [Fine Particle Dispersion 1] was dried to isolate the resin content.
[0213] <Preparation of aqueous phase> 990 parts of water, 83 parts of [microparticle dispersion 1], 37 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.), and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid. This was designated as [aqueous phase 1].
[0214] <Emulsification / solvent removal> 1,200 parts of [water phase 1] was added to the container containing [oil phase 1], and mixed with a TK homomixer at 13,000 rpm for 20 minutes to obtain [emulsified slurry 1]. Next, [emulsified slurry 1] was placed in a container equipped with a stirrer and thermometer, and the solvent was removed at 30°C for 8 hours, and then aged at 45°C for 4 hours to obtain [dispersed slurry 1].
[0215] <Washing and drying> 100 parts of [Dispersion Slurry 1] was filtered under reduced pressure, and the following operations were then carried out. (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2): 100 parts of a 10% aqueous sodium hydroxide solution was added to the filter cake of (1), mixed with a TK homomixer (at 12,000 rpm for 30 minutes), and then filtered under reduced pressure. (3): 100 parts of 10% hydrochloric acid was added to the filter cake of (2), and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4) 300 parts of ion-exchanged water was added to the filter cake of (3), mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. The above operations (1) to (4) were repeated twice to obtain a filter cake. The filtered cake was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a 75 μm mesh to obtain toner base particles 1. 100 parts of the obtained [toner base particles 1], 1.0 part of hydrophobic silica having an average particle size of 20 nm as an external additive, and 1.5 parts of hydrophobic silica having an average particle size of 120 nm were mixed using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at a peripheral speed of 30 m / sec for 30 seconds and then rested for 1 minute for 5 cycles, and then sieved through a mesh with 35 μm openings to produce [toner (1)].
[0216] (Career) A specific example of how to prepare the carrier will be described. Acrylic resin solution (50% solids) 21.0 parts Guanamine solution (70% solids) 6.4 parts Alumina particles [0.3μm, resistivity 10 14 (Ω cm)] 7.6 parts Silicone resin solution 65.0 parts [Solid content 23% (SR2410: manufactured by Toray Dow Corning Silicone Co., Ltd.)] Aminosilane 1.0 parts [Solid content 100% (SH6020: manufactured by Toray Dow Corning Silicone)] Toluene 60 parts 60 parts butyl cellosolve The above components were dispersed in a homomixer for 10 minutes to obtain a blended coating film-forming solution of acrylic resin and silicone resin containing alumina particles. Sintered ferrite powder [(MgO)1.8(MnO)49.5(Fe2O3)48.0: average particle size; 35 μm] was used as the core material, and the above coating film-forming solution was applied to the core material surface to a thickness of 0.15 μm using a Spiracoater (manufactured by Okada Seiko Co., Ltd.) and dried. The obtained carrier was left in an electric furnace at 150°C for 1 hour to be fired. After cooling, the ferrite powder bulk was crushed using a sieve with a mesh size of 106 μm to obtain a carrier. The binder resin film thickness was measured by observing the cross section of the carrier with a transmission electron microscope, and the coating film covering the carrier surface was observed, so that the average value of the film thickness was used as the film thickness. In this way, a carrier with a weight average particle size of 35 μm was obtained. 7 parts of the above [toner (1)] and 93 parts of the carrier were mixed in a Turbula mixer to obtain a developer.
[0217] Example 2 [Toner base particles 2] were obtained in the same manner as in Example 1, except that the amount of [Prepolymer A-1] was changed to 114 parts, the amount of [Prepolymer B-1] was changed to 190 parts, and the amount of [Polyester resin C-1] was changed to 798 parts in Example 1. [Toner (2)] was produced using this [Toner base particles 2].
[0218] Example 3 [Toner base particles 3] were obtained in the same manner as in Example 1, except that in Example 1, 32 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and [Prepolymer A-1] was replaced with [Prepolymer A-2], and [Polyester resin C-1] was replaced with [Polyester resin C-2]. [Toner base particles 3] were used to produce [Toner (3)].
[0219] Example 4 [Toner base particles 4] were obtained in the same manner as in Example 1, except that in Example 1, 32 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and [Prepolymer A-1] was replaced with [Prepolymer A-2], and [Polyester resin C-1] was replaced with [Polyester resin C-3]. [Toner base particles 4] were used to prepare [Toner (4)].
[0220] Example 5 [Toner base particles 5] were obtained in the same manner as in Example 1, except that in Example 1, 32 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and [Prepolymer A-1] was replaced with [Prepolymer A-3], and [Polyester resin C-1] was replaced with [Polyester resin C-2]. [Toner base particles 5] were used to produce [Toner (5)].
[0221] Example 6 [Toner base particles 6] were obtained in the same manner as in Example 1, except that in Example 1, 32 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, replacing [Prepolymer A-1] with [Prepolymer A-3], and [Polyester resin C-1] with [Polyester resin C-3]. [Toner base particles 6] were used to produce [Toner (6)].
[0222] Example 7 [Toner base particles 7] were obtained in the same manner as in Example 1, except that in Example 1, 32 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used, and 152 parts of [Prepolymer A-1] was used, and 798 parts of [Polyester resin C-3] was used, instead of [Polyester resin C-1]. [Toner base particles 7] was used to produce [Toner (7)].
[0223] Example 8 [Toner base particles 8] were obtained in the same manner as in Example 1, except that the [modified layered inorganic mineral] was not added. [Toner (8)] was produced using this [toner base particles 8].
[0224] Example 9 [Toner base particles 9] were obtained in the same manner as in Example 1, except that 811 parts of [Amorphous polyester resin C-1] and 25 parts of [Crystalline polyester resin dispersion 1] were added in <Preparation of oil phase> in Example 1. [Toner base particles 9] were used to prepare [Toner (9)]. Comparative Example 1 [Toner base particle 10] was obtained in the same manner as in Example 1, except that [Prepolymer A-1] was changed to [Prepolymer A-4] and [Prepolymer B-1] was changed to [Prepolymer B-2] in Example 1. [Toner (10)] was produced using this [Toner base particle 10].
[0225] Comparative Example 2 [Toner base particles 11] were obtained in the same manner as in Example 1, except that [Prepolymer A-1] was changed to [Prepolymer A-5] and [Prepolymer B-1] was changed to [Prepolymer B-3] in Example 1. [Toner (11)] was produced using this [Toner base particles 11].
[0226] Comparative Example 3 [Toner base particles 12] were obtained in the same manner as in Example 1, except that 44 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used and the homogenization process using a bead mill was omitted. [Toner base particles 12] was produced using this [toner base particles 12].
[0227] Comparative Example 4 In Example 1, a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.) was used at 32 parts, the homogenization process using a bead mill was omitted, and [Prepolymer A-1] was changed to 152 parts of [Prepolymer A-3] and [Polyester Resin C-1] to 798 parts of [Polyester Resin C-3] in the same manner as in Example 1 to obtain [Toner Base Particles 13]. [Toner (13)] was produced using this [Toner Base Particles 13].
[0228] Comparative Example 5 [Toner base particles 14] were obtained in the same manner as in Example 1, except that [Prepolymer B-1] was not added and [Polyester resin C-1] was changed to [Polyester resin C-4] in Example 1. [Toner (14)] was produced using this [Toner base particles 14].
[0229] Comparative Example 6 [Toner base particles 15] were obtained in the same manner as in Example 1, except that [Prepolymer A-1] was not added and [Polyester resin C-1] was changed to [Polyester resin C-5] in Example 1. [Toner (15)] was produced using this [Toner base particles 15].
[0230] Next, the test and measurement methods related to the present invention will be described.
[0231] <Toner Tg1st, glass transition temperatures of polyester resins A, B and C> 1 g of toner was put into 100 mL of THF and Soxhlet extraction was performed to obtain THF soluble and insoluble fractions. This was then dried in a vacuum dryer for 24 hours to obtain polyester resin C from the THF soluble fraction and a mixture of polyester resin A and polyester resin B from the THF insoluble fraction. These were used as the target samples. In addition, the toner was used as the target sample when measuring the toner Tg1st.
[0232] Next, about 5.0 mg of the target sample was placed in an aluminum sample container, the sample container was placed on a holder unit, and set in an electric furnace. Next, under a nitrogen atmosphere, the sample was heated from -80°C to 150°C at a heating rate of 10°C / min (first heating). After that, the sample was cooled from 150°C to -80°C at a heating rate of 10°C / min, and further heated to 150°C at a heating rate of 10°C / min (second heating). In each of the first and second heating, a DSC curve was measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments). From the obtained DSC curves, the DSC curve at the first heating was selected using the analysis program in the Q-200 system, and the glass transition temperature Tg1st at the first heating of the target sample was calculated. Similarly, the DSC curve at the second heating was selected, and the glass transition temperature Tg2nd at the second heating of the target sample was calculated.
[0233] The toner is subjected to Soxhlet extraction to obtain THF soluble and insoluble fractions. These are then dried in a vacuum dryer for 24 hours to obtain a mixture (1) of polyester resin C and crystalline polyester resin from the THF soluble fraction. Also, a mixture (2) of polyester resin A and polyester resin B is obtained from the THF insoluble fraction. For mixture (1), the masses of the obtained mixture (1) and mixture (2) are measured, and the mass ratio of mixture (1) to their total is calculated to obtain the mass ratio of polyester resin C to the crystalline polyester resin. In addition, for mixture (2), the masses of the obtained mixture (1) and mixture (2) are measured, and the mass ratio of mixture (2) to their total is calculated to obtain the mass ratio of polyester resin A + polyester resin B. Table 1 shows the composition ratio of the toner, Tga1st, Tgb1st, Tg1st, glass transition temperatures of polyester resins A, B and C, and physical properties of the toner.
[0234] (evaluation) The toners (1) to (15) obtained above were evaluated as follows, either as a single toner or as a developer. <Fixability (minimum fixing temperature)> Using a modified RICOH MP C5503 machine, transfer paper (manufactured by Ricoh Business Expert Co., Ltd., copy printing paper <70> ) and the amount of toner adhered after transfer is 0.85±0.02mg / cm 2 A solid image (image size 3 cm x 8 cm) was created over the entire surface of the paper, and fixing was performed by changing the temperature of the fixing belt. The surface of the fixed image obtained was then drawn on using a drawing tester AD-401 (manufactured by Ueshima Seisakusho) with a ruby needle (tip radius 260 μmR to 320 μmR, tip angle 60 degrees) and a load of 50 g. The drawn surface was then rubbed strongly five times with a fiber (Honeycott #440, manufactured by Honeylon Co., Ltd.). The fixing belt temperature at which the image was almost completely scraped off was determined as the minimum fixing temperature. A solid image was formed on the transfer paper at a position 3.0 cm from the leading edge in the paper feed direction. The lower the minimum fixing temperature, the better the low-temperature fixing property.
[0235] <Heat-resistant storage stability (penetration)> Each toner was filled into a 50 mL glass container and left in a thermostatic chamber at 50° C. for 24 hours. The toner was cooled to 24° C., and the penetration (mm) was measured using a penetration test (JIS K2235-1991) and evaluated based on the following criteria. Note that a larger penetration value indicates better heat resistance storage stability, and a penetration value of less than 5 mm is likely to cause problems in use. In the present invention, the penetration degree is expressed as a penetration depth (mm). [Evaluation Criteria] ◎: Penetration 25mm or more ○: Penetration 15mm or more and less than 25mm △: Penetration 5mm or more and less than 15mm ×: Penetration less than 5mm Furthermore, "◎" and "○" are in the good range (passing criteria).
[0236] <Charge stability> Using a modified RICOH MP C5503, a durability test was conducted to print 10,000 charts continuously with an image area ratio of 2%, and the change in the charge amount at that time was evaluated. 1g of developer was weighed, and the change in the charge amount was determined by the blow-off method. Similarly, a durability test was conducted to print 10,000 charts continuously with an image area ratio of 60%, and the change in the charge amount at that time was evaluated. 1g of developer was weighed, and the change in the charge amount was determined by the blow-off method. The value with the larger difference between the two charge amounts was used. (Blow-off method) The developer was placed in a cylindrical Faraday cage with wire mesh on both ends, and the toner was blown off from the developer using high-pressure air. The amount of residual charge was then measured using an electrometer. The weight of the toner in the developer was calculated from the difference in the weight of the Faraday cage before and after the blow-off. [Evaluation Criteria] ◎: Change in charge amount is 3μc / g or less ○: The change in charge amount is more than 3μc / g and less than 5μc / g △: The change in charge amount is more than 5 μc / g and less than 10 μc / g ×: The change in charge amount is more than 10 μc / g Furthermore, "◎" and "○" are in the good range (passing criteria).
[0237] The evaluation results are shown in Table 2.
[0238] [Table 1]
[0239] [Table 2]
[0240] The embodiment of the present invention is, for example, as described below. (1) A toner for developing an electrostatic image, comprising a toner base and an external additive attached to a surface of the toner base, The toner base contains at least a binder resin, a colorant, and a release agent. The toner contains a component insoluble in tetrahydrofuran (THF) and a component soluble in THF, The components of the toner that are insoluble in tetrahydrofuran (THF) are observed at two points, Tga1st and Tgb1st, in the first temperature rise of differential scanning calorimetry (DSC), The Tga1st is -40°C or more and 10°C or less, and the Tgb1st is 45°C or more and 65°C or less, A toner for developing electrostatic images, characterized in that the amount of residual surfactant in the toner as detected by liquid chromatography / mass spectrometry (LC / MS) is 800 ppm or more and 1,200 ppm or less. (2) The toner has a glass transition temperature (Tg1st) in the first temperature rise measured by differential scanning calorimetry (DSC) of 45° C. or more and 65° C. or less; The tetrahydrofuran (THF) insoluble component of the toner includes a polyester resin A having a glass transition temperature (Tg2nd) in the second heating period measured by DSC of -50°C or more and 0°C or less, and a polyester resin B having a glass transition temperature (Tg2nd) in the second heating period measured by DSC of 45°C or more and 65°C or less, The toner for developing electrostatic images according to the above (1), wherein the THF-soluble component of the toner contains a polyester resin C having a glass transition temperature (Tg2nd) in the second heating cycle of DSC of 45° C. or more and 65° C. or less. (3) The toner for developing electrostatic images according to the above (1) or (2), wherein the toner base contains a modified layered inorganic mineral obtained by modifying at least a part of the interlayer ions of a layered inorganic mineral with an organic ion. (4) The toner for developing electrostatic images according to any one of the above (1) to (3), wherein a liberation rate A (% by mass) of silica from the toner satisfies the relationship of the following formula (1): 0.5≦A<1.0...Equation (1) (5) The toner for developing electrostatic images according to any one of the above (2) to (4), wherein, when a is a mass ratio of the polyester resin A, b is a mass ratio of the polyester resin B, and c is a mass ratio of the polyester resin C relative to the total mass of the polyester resin A, the polyester resin B, and the polyester resin C, the a, the b, and the c satisfy the relationship of the following formula (2): 4(a+b) <c ···(2) (6) The toner for developing electrostatic images according to any one of (1) to (5) above, wherein the mass average particle diameter D4 of the toner is 3 μm or more and 7 μm or less, and the ratio D4 / Dn of the mass average particle diameter D4 to the number average particle diameter Dn is 1.00 or more and 1.20 or less. (7) The toner for developing electrostatic images according to any one of (1) to (6), wherein the toner has an average circularity of 0.95 or more and 0.99 or less. (8) A toner storage unit, characterized in that it stores the toner according to any one of (1) to (7) above. (9) A two-component developer comprising the toner according to any one of (1) to (7) above and a carrier. (10) A method for producing a toner image comprising: an electrostatic latent image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier; and a developing means having a toner for developing the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, 8. An image forming apparatus, comprising the toner according to any one of (1) to (7) above. (11) The image forming apparatus according to (10) above, further comprising a process cartridge that integrally supports the electrostatic latent image carrier and at least the developing means and is detachably mountable to a main body of the image forming apparatus. (12) forming an electrostatic latent image on an electrostatic latent image carrier; a developing step of developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image, 8. An image forming method, comprising the toner according to any one of (1) to (7) above. [Explanation of symbols]
[0241] 10 Intermediate transfer body 14, 15, 16 Support rollers 17 Intermediate transfer body cleaning device 18 Image forming means 20 Tandem image forming device 21 Exposure equipment 22 Secondary transfer device 23 Laura 24 Secondary transfer belt 25 Fixing device 26 Fixing belt 27 Pressure roller 28 Sheet reversing device 30 Manuscript holder 32 Contact Glass 33 First Running Body 34 Second Running Body 35 Imaging Lens 36 Reading sensor 40 Photoreceptor 42 Paper feed roller 43 Paper Bank 44 Paper feed cassette 45 Separation roller 46 Paper feed path 47 Transport roller 48 Paper feed path 49 Registration roller 50 Paper feed roller 51 Manual feed tray 52 Separation roller 53 Paper feed path 55 Switching claw 56 Discharge roller 57 Output tray 71 Process cartridge 72 Photoreceptor 73 Charging means 74 Developing means 75 Cleaning Method 100 Copying device body 120Bk, 120C, 120M, 120Y Image writing section 130Bk, 130C, 130M, 130Y Image forming section 140 Paper feed section 150 Fixing device 160 Registration roller pair 200 Paper feed table 210Bk, 210C, 210M, 210Y photoconductor 215Bk, 215C, 215M, 215Y Charging device 200Bk, 200C, 200M, 200Y developing device 220 Intermediate transfer belt 230Bk, 230C, 230M, 230Y Primary transfer device 241, 242, 243 Conductive roller 260 Intermediate transfer belt cleaning device 261, 262 Conductive fur brush 300 Scanner 300Bk, 300C, 300M, 300Y cleaning device 400 Automatic Document Feeder ADF 500 Transfer Belt 502 Pre-transfer charger 502a Discharge Wire 502b Grid electrode 502c Casing 600 Secondary transfer roller 803 Power supply 241, 242, 243 Conductive roller [Prior art documents] [Patent documents]
[0242] [Patent Document 1] Japanese Patent Application Publication No. 11-133665 [Patent Document 2] JP 2004-46095 A [Patent Document 3] JP 2007-271789 A [Patent Document 4] JP 2015-52697 A [Patent Document 5] JP 2015-118151 A [Patent Document 6] JP 2016-164616 A [Patent Document 7] Patent No. 5884797
Claims
1. A toner for developing an electrostatic image, comprising a toner base and an external additive attached to a surface of the toner base, The toner base contains at least a binder resin, a colorant, and a release agent. The toner contains a component insoluble in tetrahydrofuran (THF) and a component soluble in THF, The components of the toner that are insoluble in tetrahydrofuran (THF) are observed at two points, Tga1st and Tgb1st, in the first temperature rise of differential scanning calorimetry (DSC). The Tga1st is −40° C. or more and 10° C. or less, and the Tgb1st is 45° C. or more and 65° C. or less, 1. A toner for developing an electrostatic image, comprising: a toner having a residual surfactant content of 800 ppm or more and 1,200 ppm or less as detected by liquid chromatography / mass spectrometry (LC / MS method).
2. the toner has a glass transition temperature (Tg1st) in a first temperature rise measured by differential scanning calorimetry (DSC) of 45° C. or higher and 65° C. or lower; The tetrahydrofuran (THF) insoluble component of the toner includes a polyester resin A having a glass transition temperature (Tg2nd) in the second heating period of a DSC of −50° C. or more and 0° C. or less, and a polyester resin B having a glass transition temperature (Tg2nd) in the second heating period of a DSC of 45° C. or more and 65° C. or less, 2. The toner for developing electrostatic images according to claim 1, wherein the THF-soluble component of the toner contains a polyester resin C having a glass transition temperature (Tg2nd) in a second heating run of a DSC of 45° C. or more and 65° C. or less.
3. 3. The toner for developing electrostatic images according to claim 1, wherein the toner base contains a modified layered inorganic mineral obtained by modifying at least a part of the interlayer ions of a layered inorganic mineral with an organic ion.
4. The toner for developing an electrostatic image according to claim 1 , wherein a liberation rate A (mass %) of silica from the toner satisfies the relationship of the following formula (1): 0.5≦A<1.0...Formula (1)
5. 3. The toner for developing an electrostatic image according to claim 2, wherein, when a is a mass ratio of the polyester resin A, b is a mass ratio of the polyester resin B, and c is a mass ratio of the polyester resin C with respect to a total mass of the polyester resin A, the polyester resin B, and the polyester resin C, the a, the b, and the c satisfy the relationship of the following formula (2): 4(a+b)<c...(2)
6. 3. The toner for developing electrostatic images according to claim 1, wherein the toner has a mass average particle diameter D4 of 3 μm or more and 7 μm or less, and a ratio D4 / Dn of the mass average particle diameter D4 to the number average particle diameter Dn is 1.00 or more and 1.20 or less.
7. 3. The toner for developing electrostatic images according to claim 1, wherein the average circularity of the toner is 0.95 or more and 0.99 or less.
8. A toner storage unit, comprising the toner according to claim 1 or 2 stored therein.
9. 3. A two-component developer comprising the toner according to claim 1 or 2 and a carrier.
10. a developing unit provided with a toner for developing the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, 3. An image forming apparatus, comprising the toner according to claim 1 or 2.
11. 11. The image forming apparatus according to claim 10, further comprising a process cartridge which integrally supports the electrostatic latent image carrier and at least the developing means and is detachably mountable to a main body of the image forming apparatus.
12. an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier; a developing step of developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image, 3. An image forming method, comprising the toner according to claim 1 or 2.
Citation Information
Patent Citations
Method of treating tip of binding thread of japanese bound booklet
JP1983084797A
Dry toner
JP1999133665A
Color toner for developing electrostatic charge image
JP2004046095A
Toner binder and toner
JP2007271789A
Toner, developer, and image forming apparatus
JP2015052697A